Sustainable aviation fuels: a review of production technologies, life-cycle emissions, and key challenges - Aaqib Zafar; Muhammad Nauman; Muhammad Usman; Rashid Ali Laghari; Muhammad Imran Akhtar; Azhar Abbas Khosa; Muhammad Kashif Shahzad; Abdur Rahman Shaukat; Sheikh Muhammad Farhan; Muhammad Hamid Abbas; Longfei Chen (Fuel, 2027)

Identification of plastome-derived mini barcodes by DNA metabarcoding and comparative effectiveness to decipher their strength and resolving power for taxonomic topology-based phylogenetic determination of Chenopodium quinoa - Zakia Habib; Siddra Ijaz; Imran Ul Haq; Irfan Afzal; Ghulam Muhammad Ali (Molecular Biology Reports, 2026)

Next-generation hybrid membranes integrating MXene and MOF architectures for energy-efficient water treatment - Saleem Raza; Luqman Ali; Muhammad Usman Hameed; Sidra Khalid; Sundas Shoukat; Mamuna Ahmad; Liguo Shen; Ghafar Ali; Imran Shakir (Desalination, 2026)

Can host genetics transform the sustainable control of tropical theileriosis? Insights from the Tick-Theileria interface - Abdullah Azeem; Muhammad Kasib Khan; Muhammad Shahid Mahmood; Rao Zahid Abbas; Muhammad Umer Ashraf; Sultan Ali; Muhammad Adnan Sabir Mughal; Zaheer Abbas; Sundas Afresham; Mehroz Latif; Muhammad Imran; Zia ud Din Sindhu (Veterinary Parasitology, 2026)

Hydrogen bonding implications on sweetness behavior of sugar alcohols in food model systems: A thermophysical and FTIR study - Uzma Shahazidy; Muhammad Asghar Jamal; Muhammad Imran; Muhammad Fakhar-e-alam; Arshad Ali (Food Research International, 2026)

Retraction notice to ‘Nano-remediation technologies for the sustainable mitigation of persistent organic pollutants’ [Environ. Res. 211 (2022) 113060] - Liu Fei; Muhammad Bilal; Sarmad Ahmad Qamar; Hafiz Muhammad Imran; Areej Riasat; Muhammad Jahangeer; Misbah Ghafoor; Nisar Ali; Hafiz M.N. Iqbal (Environmental Research, 2026)

Recent advances in electrochemical ion separation: Materials, mechanisms and sustainable applications for water and resource recovery - Luqman Ali; Abdul Majid Khan; Muhammad Usman Hameed; Saleem Raza; Liguo Shen; Imran Shakir; Muhammad Hafeez (Desalination, 2026)

Exploring the Molecular Mechanism of Arbutin as a Potential Inhibitor Against Melanoma: Insights from Network Pharmacology, Molecular Docking, Dynamics Simulations, and DFT Analysis - Md Rashedul Islam; Ishtiaq Qadri; Muhammad Afzal; Misbahuddin Rafeeq; Abdullah Alfaifi; Khadijah Abdullah Alfaifi; Sami I. Alzarea; Ehab M. M. Ali; Imran Kazmi (Journal of Pharmaceutical Innovation, 2026)

Contamination levels, eco-health risks, and source identification of some potentially toxic elements in roadside dust along the Indus Highway (N-55), Pakistan using compositional data analysis - Amanullah; Wajid Ali; Saad Khan; Said Muhammad; Abdur Raziq; Muhamamd Nafees; Imran Ud Din (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Engineering abiotic stress tolerance in cereal crops: current advances and future directions - Baber Ali; Abdul Rehman; Arafat Abdel Hamed Abdel Latef; Muhammad Imran; Muhammad Ammar Javed; Nathan Wise; Nijat Imin (Cereal Research Communications, 2026)

Vitamin B12 and pregabalin combination restored brain waves dynamics and behavior in chronic unpredictable mild stress (CUMS) model of depression - Zain Raza; Muhammad Hussain Ali; Zohabia Rehman; Waseem Ashraf; Fakhir Hannan; Imran Imran; Faleh Alqahtani (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Evaluation of anti-diabetic potential of Fagonia indica leaf, seed, and flower extracts via phytochemical profiling, In Vitro, In Silico, and In Vivo approaches - Muhammad Azmat; Muhammad Yasin Ashraf; Naila Ali; Imran Zafar; Ahsanullah Unar; Mohamed Mohany (Phytochemistry Letters, 2026)

Pollution Indices as Useful Tools for Comparative Potential Health Risks of Nickel in Water-Soil-Fodder-Animals Food Chain in Relation to Spatial and Temporal Fluctuations - Hamid Raza; Mukkram Ali Tahir; Noor Us Sabah; Muhammad Imran; Rameez Hussain; Muhammad Tariq (Biological Trace Element Research, 2026)

Deciphering the synergy of eudragit and polyethylene glycol supported cobalt oxide for catalytic, electrocatalytic and antibacterial activity: Computational insights - Atika; Muhammad Imran; Iram Shahzadi; Ali Haider; Sumaira Rasool; Anwar Ul-Hamid; Norah A. Albassami; Muhammad Ikram (Journal of Water Process Engineering, 2026)

Multilevel barriers to antimicrobial stewardship in tertiary care hospitals: A comparative systematic scoping review of high-income versus low-/middle-income countries evidence mapped by study design and healthcare professionals - Azfar Athar Ishaqui; Zikria Saleem; Tauqeer Hussain Mallhi; Sultan M. Alshahrani; Khalid Orayj; Salman Ashfaq Ahmad; Rayah Asiri; Emad Ali Alsaleh; Muhammad Imran; Mohammed Ali Kaddoura; Bilal Jawed; Narendar Kumar; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Advances in functional carbon composites for electrochemical energy conversion and catalysis: Design strategies, mechanisms and future prospects - Luqman Ali; Muhammad Usman Hameed; Xingfen Huang; Saleem Raza; Abdul Majid Khan; Mashkoor Ahmad; Akif Safeen; Imran Shakir (Journal of Environmental Chemical Engineering, 2026)

Integrated facies analysis and diagenetic impact on carbonate reservoirs: a case study from Jurassic shallow marine carbonate platform, NW Himalayas, Pakistan - Ihsan Ullah; Muhammad Jamil; Hamad ur Rahim; Imran Khan; Wahid Abbas; Asad Ali; Mohib Ur Rehman (Carbonates and Evaporites, 2026)

Human development under environmental and socioeconomic pressures: an ARDL-based assessment of life expectancy in Pakistan - Muhammad Khalid Anser; Muhammad Imran; Helmi Ali Mkaouar; Jameel Ahmad Khader; Alaa Shoukry; Wasfi Yengui; Kamran Azam; Khalid Zaman (Air Quality, Atmosphere & Health, 2026)

Host–Microbiota Metabolic Interactions in Atherosclerosis: Oral, gut, and Blood Perspectives - Ikram Khan; Muhammad Irfan; Ali Sher Bacha; Imran Khan; Yasir Ali; Zhiqiang Li (Probiotics and Antimicrobial Proteins, 2026)

Insecticidal and antibacterial potential of Croton tiglium functionalized zinc oxide nanoparticles - Arshad Ali; Ali Hassan; Imran Afzal; Hammad Hassan; Kirshan Chand; Hafiz Muhammad Usman; Xiaolong Liu; Min Lu (International Journal of Tropical Insect Science, 2026)

Trade adjusted carbon emissions and renewable energy electricity output: Evidence from method of moment quantile regression for N-11 economies - Maaz Amin; Salman Wahab; Bilal Ahmed; Muhammad Imran; Shahid Ali; Sakiru Adebola Solarin (Environment, Development and Sustainability, 2026)

Light and temperature differentially influence morphology, phytohormone profiles, and phenolic acid biosynthesis in Allium sativum across developmental stages - Muhammad Jawaad Atif; Bakht Amin; Muhammad Imran Ghani; Muhammad Ali; Zhihui Cheng (Biologia, 2026)

A novel spatiotemporal and machine learning framework for sustainable groundwater monitoring and management - Sheraz Maqbool; Muhammad Imran Khan; Aamir Raza; Mumtaz Ali; Naeem Saddique; Qaisar Saddique (Groundwater for Sustainable Development, 2026)

A comprehensive review of the phytochemical, and pharmacological potential of Alnus hirsuta (Spach) Rupr., (Siberian Alder): implications for anti-inflammatory therapeutics - Sajid Ali; Adnan Amin; Muhammad Saeed Akhtar; Khizar Abdullah Khan; Ishaq N. Khan; Imran Khan; Wajid Zaman; Atif Ali Khan Khalil (Inflammopharmacology, 2026)

α-Pinene alleviates inflammatory responses and oxidative stress in freund’s complete adjuvant induced arthritic rat model and associated risk factors of atherosclerosis - Khadija Ali; Iqral; Ali Sharif; Bushra Akhtar; Ayesha Younas; Muhammad Ali; Muhammad Furqan Akhtar; Muhammad Imran Khan; Ahmed Al-Harrasi; Aftab Ahmad (Inflammopharmacology, 2026)

The biological synthesis of iron oxide nanomaterials and their possible physiological and biochemical toxicities in Cyprinus carpio - Nadia Bibi; Nishita Narwal; Muhammad Anees; Huma Ayub; Mian Adnan Kakakhel; Tawaf Ali Shah; Ashraf Khalifa; Imran Ibrahim Shaikh (Ecotoxicology, 2026)

Unraveling survival disparities in primary central nervous system (CNS) lymphoma: an analysis of race, socioeconomic factors, and treatment outcomes using the surveillance, epidemiology, and end results program (2000–2021) - Shahzaib Maqbool; Mohammad Ebad Ur Rehman; Ramesha Tahir; Hafsa Arshad Azam Raja; Mouzma Ali; Muhammad Ibrahim; Jacob Guerrero; Abdur Rehman; Imran Khan; Abat Khan; Jose D. Sandoval-Sus (Cancer Causes & Control, 2026)

Rethinking lice management at the human–animal interface: challenges, green alternatives, and the road ahead - Rimsha Jamil; Muhammad Imran; Muhammad Adnan Sabir Mughal; Rao Zahid Abbas; Muhammad Umar Ijaz; Muhammad Kasib Khan; Asghar Abbas; Farhan Ahmad Atif; Sultan Ali (International Journal of Tropical Insect Science, 2026)

The impact of green brand image and green perceived risk on green trust and green purchase intention: the moderating role consumption values - Bilal Ahmed; Salman Wahab; Muhammad Imran; Muhammad Imran; Nawaz Ali Shah; Shamsher Ali (Environment, Development and Sustainability, 2026)

Comparative analysis of machine learning and neural network models for petrophysical property prediction in heterogeneous reservoirs - Zayan Khursheed; Muhammad Anas Jawaid; Muhammad Mustafa; Shaine Mohammadali Lalji; Syed Imran Ali; Mohsin Ayubi (Next Research, 2026)

Selenium supplementation and male fertility: Mechanistic insights and therapeutic potential - Neeraj Patel; Riya Mishra; Muhammad Afzal; Surya Nath Pandey; Haider Ali; Nardev Singh; Rakhi Mishra; Mohd Imran (Journal of Trace Elements in Medicine and Biology, 2026)

Facile and Low Cost Synthesis of NiFe-LDH/ZnO Composites for Efficient Photodegradation of MB in Aqueous Solution Under the Illumination of Natural Sunlight - Ramsha Saleem; Humera Shaikh; Muhammad Saajan Barhaam; Qurban Ali Shah; Baradi Waryani; Mazhar Ali Abbasi; Imran Ali Halepoto; Nek Muhammad Shaikh; Muhammad Ali Bhatti; Rafat M. Ibrahim; Elmuez Dawi; Aneela Tahira; et al. (Water, Air, & Soil Pollution, 2026)

Retraction Note: Trilemma assessment of energy intensity, efficiency, and environmental index: evidence from BRICS countries - Zulifqar Ali Baloch; Qingmei Tan; Nadeem Iqbal; Muhammad Mohsin; Qaiser Abbas; Wasim Iqbal; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2026)

Harnessing novel biosynthesized ZrO₂ biochar nanocomposites for reactive orange 16 dye adsorption: kinetic modeling and cytotoxicity insights - Mubashara Fayyaz; Mohamed A. Habib; Syed Kashif Ali; Saif Ullah; Muhammad Imran Kanjal; Tahreem Saleem; Rana Muhammad Zulqarnain; Ahmed B. M. Ibrahim (Biodegradation, 2026)

Facile fabrication of NiO/MnO2/CuO nanocomposite as robust electrode material for electrochemical water splitting - Atif Nazir; Chanda Sehar; Muhammad Fahad Saeed; Areej Fatima; Wael dheaa Kadhim; Zainab Ahmed Abass; Imran Shakir; Aboud Ahmed Awadh Bahajjaj; Muhammad Ali Khan; S. Shah (Fuel, 2026)

Temperature-responsive regulation of combined drip and micro-sprinkler systems in greenhouses: an EWM-TOPSIS approach for enhancing tomato heat resilience and irrigation efficiency - Chuan Zhang; Run Xue; Haofang Yan; Imran Ali Lakhiar; Jiangtao Ren; Kinde Negessa Disasa; Muhammad Akhlaq; Shuaishuai Deng (Irrigation Science, 2026)

Retraction Note: Novel acetamide derivatives of 2-aminobenzimidazole prevent inflammatory arthritis in rats via suppression of pro-inflammatory mediators - Aymun Madni Zubair; Muhammad Nasir Hayat Malik; Waqas Younis; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Alamgeer Yuchi; Muhammad Naveed Mushtaq; Romeeza Tahir; Muhammad Bilal Sarwar; Muhammad Roman; Ayaz Ali Khan; et al. (Inflammopharmacology, 2026)

Fruit yield estimation of kinnow mandarin (Citrus reticulata) orchards – integrating canopy physiology with remote sensing - Ansar Ali; Muhammad Imran; Touqeer Ahmad; Ghulam Abbas (Arabian Journal of Geosciences, 2026)

Current progress in pathway-targeted therapeutics for Alzheimer’s disease: mechanistic insights and windows of opportunity - Habab Ali Ahmad; Mahnoor Zafar; Tooba Khan; Muhammad Imran Khan (Molecular and Cellular Biochemistry, 2026)

Genome-wide identification, functions, and expression analysis of carbonic anhydrase gene family in the gills of O. niloticus under salinity stress - Ahmad Waheed; Samra Farooq; Jabbir Ali Khan; Imran Ahmad Khan; Samra Shafqat; Hina Naz; Muhammad Saleem Khan; Muhammad Wajid (Aquaculture, 2026)

Water Quality deterministic and Probabilistic Health Risks Assessment using Monte Carlo Simulation: Case Study from a Semi-Arid Region - Said Muhammad; Zeeshan Raza; Wajid Ali; Ashfaq Ahmad; Cem Tokatli; Imran Ud Din (Water, Air, & Soil Pollution, 2026)

Marine Drug Design for Epitheliocytis Rendering AI ‐Assisted Bioisosteric Replacement of Salicin - Muhammad Naveed; Khushbakht Javed; Tariq Aziz; Rahmana Wazir; Imran Ali; Ayaz Ali Khan; Ashwag Shami; Maher S. Alwethaynani; Fahad Al‐Asmari; Fakhria A. Al‐Joufi (Journal of Fish Diseases, 2026)
Epitheliocystis is a distinctive and relatively understudied bacterial infection of finfish skin and gill epithelia that occurs intracellularly and results in the enlargement of the host cells. The Candidatus Syngnamydia salmonis is a bacterial pathogen that affects fish, especially salmon species like trout and salmon. The production of Epitheliocystis by Candidatus Syngnamydia salmonis poses several challenges to the aquaculture industry. Currently, limited drugs and therapies are available to effectively manage and cease the spread of this disease. The goal of this study was to develop a potential drug target for the treatment of epitheliocystis. Salicin, an organic glucoside widely known for its anti‐inflammatory characteristics, was chosen as the initial compound because of its pharmacological significance and confirmed as a bioisostere (a compound with identical biological activities but a different structure). The Xundrug MolOpt AI generative model of bioisosteric replacement tool was chosen as the optimisation technique in a cognitive exertion to improve the novel drug candidate salicin by its AI‐assisted bioisosteric replacement. To retrieve the docking results, the top three ligands from Xundrug and the cell division protein of Candidatus Syngnamydia salmonis were uploaded to the HDOCK web server, which utilises a hybrid docking technique combining template‐based modelling for docking. The target drug candidate was selected based on model 17's highest docking score of 135.6 kcal/mol. Furthermore, the Lipinski rule of five and the ADMET properties of the Bioisosteric Replaced Salicin model 17 (BRS‐17) were carefully explored. The results showed that BRS‐17 fulfilled the pharmacophore characteristics criteria, hence making it an ideal target candidate for Candidatus Syngnamydia salmonis' cell division protein. Additionally, the results are supported by −6.735Kcal/mol docking score predicted by DockThor. With the help of the supporting information from this study, the proposed drug design can close the gap in earlier studies for resistance to antibiotic treatments. It is suggested that in vitro tests be performed on this drug to show the effectiveness of the suggested design.

Retraction notice to “Almond shell-derived biochar decreased toxic metals bioavailability and uptake by tomato and enhanced the antioxidant system and microbial community” [Sci. Total Environ. 929 (2024) 172632] - Muhammad Imran Ghani; Mohammad Abass Ahanger; Tanveer Ali Sial; Sajjad Haider; Junaid Ali Siddique; Ruidong Fan; Yanjiang Liu; Esmat F. Ali; Manish Kumar; Xing Yang; Jörg Rinklebe; Xiaoyulong Chen; et al. (Science of The Total Environment, 2026)

Evaluating synergistic toxicology effects of mixed microplastics on marine micro crustacean Artemia salina - Mariam Ali; Hira Amjad; Imran Hashmi; Hassan Shafiq; Noreddine Ghaffour; Muhammad Saqib Nawaz (Regional Studies in Marine Science, 2026)

Wheat-Berseem intercropping system enhances soil fertility, carbon sequestration and crop productivity under nutrient-deficient conditions - Zafar Iqbal; Sundas Bilal; Sana ur Rehman; Imran Haider; Maryam Saeed; Maqshoof Ahmad; Muhammad Ali Raza; Mehraj A. Abbasov; Walid Soufan (Plant and Soil, 2026)

Exploring smart solutions for stressed soils: dual-action of culture filtrates and nanoparticles for sustainable onion cultivation - Muhammad Imran; Maryam M. Alomran; Hanan A. Khalifa; Muhammad Saqib Bilal; Atef F. Ahmed; Esmat F. Ali; Abeer S. Alqurashi; Munirah F. Aldayel; Kamal A. M. Abo-Elyousr (European Journal of Plant Pathology, 2026)

Unlocking geothermal potential in abandoned hydrocarbon and exploration wells: a sustainable energy solution - Muhammad Affan Uddin Ali Khan; Syed Imran Ali; Shaine Muhammadali Lalji; Aliza Hussain; Wajih Hasan; Munira Akhtar Khan; Syed Danish Rasool (Arabian Journal of Geosciences, 2026)

Investigating the Wound Healing Potential of CuCO3 Nanoparticles in Alloxan-Induced Diabetic Albino Mice: An Experimental and In Silico Approach - Muhammad Saqib Rafiq; Jabbir Ali Khan; Ashfaq Ahmad Shah Bukhari; Samra Shafqat; Ahmad Waheed; Muhammad Yasir Abbas; Muhammad Waseem Aslam; Imran Ibrahim Shaikh; Khalid S. Almaary; Muhammad Saleem Khan (Biological Trace Element Research, 2025)

Biphasic synthesis of Pd/Ovs-TiO₂ (black) for efficient moxifloxacin degradation and toxicity mitigation - Muhammad Imran Kanjal; Iram Yasmin; Syed Kashif Ali; Muhammad Wasim Afzal; Muhammad Irfan Ahamad; Mohamed A. Habib; Ahmed B.M. Ibrahim; Rana Muhammad Zulqarnain (Journal of Water Process Engineering, 2025)

Recent advances in biochar-based materials for CO₂ capture: From preparation to application in value-added chemicals and fuels - Maroof Ali Panhwar; Boxi Geng; Bachirou Guene Lougou; Muhammad Rafique; Imran Ali; Rehan Khursheed; Akhil Garg; Yong Shuai (Journal of Environmental Chemical Engineering, 2025)

Innovative Fe-F-Co-doped NiO nanoarrays: Pioneering high-efficiency electrochemical nitrate reduction to ammonia - Anum Bilal; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Ibrahim Khan; Imran Mahmood Khan; Muhammad Sajjad; Shahid Ali; Nicholas M. Musyoka; Guocong Liu; Abd-ElAziem Farouk; Nouf M. Alyami (Journal of Environmental Chemical Engineering, 2025)

Engineering multifunctional fire proof superhydrophobic cotton fabric via sequential coating of flower-like PPPA/BMOF and PDMS - Tooba Ali; Naseer Ahmad; Waqas Ahmad; Hua-Ming Xiao; Syed Muhammad Jawad; Muhammad Imran Malik; Dilshad Hussain (Chemical Engineering Journal, 2025)

Phenotypic Plasticity of Safflower Genotypes in Response to Contrasting Climatic Conditions - Obaid Afzal; Mukhtar Ahmed; Sahir Hameed Khattak; Muhammad Aqeel Aslam; Saida Komal; Maryam Murtaza; Farrukh Bashir; Aqeel Ahmad; Aliya Mirbaz; Haroon Ur Rasheed; Ghulam Muhammad Ali; Muhammad Usman; et al. (Plant Molecular Biology Reporter, 2025)

Identification of a biallelic MMUT variant (p.Thr230Arg) and its global perspective on clinical management - Sumreena Mansoor; Qamar Ali; Sabeen Abid Khan; Munir Iqbal Malik; Muhammad Imran; Raheel Qamar; Maleeha Azam (Molecular Biology Reports, 2025)

Consortium of Endophytic Bacillus australimaris CK11 and Staphylococcus epidermidis CK9 from Commiphora gileadensis Mediates Tomato Resilience to Combined Salinity, Heat, and Drought Stresses - Syed Saad Jan; Nasir Ali Khan; Sajjad Asaf; Raheem Shahzad; Lubna; Muhammad Imran; Saqib Bilal; In-Jung Lee; Ahmed Al-Harrasi (Journal of Plant Growth Regulation, 2025)

Green Synthesis of Mangifera Indica Mediated NiO and NiMn2O4 Nanomaterials for Electrocatalytic Water Splitting - Fatima Masood; Shabbir Hussain; Muhammad Arif; Shahzad Murtaza; Muhammad Imran; Muhammad Bilal Tahir; Khurram Shahzad Munawar; Hamad M. Alkahtani; Amer Alhaj Zen; Syed Adnan Ali Shah (International Journal of Environmental Research, 2025)

Improving Soil Fertility, Seed Yield, and Oil Quality of Sunflower Through Application of Processed Animal Manure Under Rainfed Conditions - Ghulam Abbas Shah; Mughees Mustafa; Zheli Ding; Zahid Mahmood; Faheem Khan; Shujaat Hussain Khan; Safdar Ali; Ghulam Mustafa Shah; Imran Mahmood; Muhammad Bilawal Junaid; Munirah Abdullah Al-Dosary; Muhammad Habib Ur Rehman; et al. (International Journal of Plant Production, 2025)

Transgenic AVP1 wheat (Triticum aestivum L.) inoculated with plant growth-promoting Azospirillum strains improves biomass and grain yield - Muhammad Sajid; Tahir Naqqash; Muhammad Arshad; Tawaf Ali Shah; Turki M. Dawoud; Mohammed Bourhia; Imran Habib (Cereal Research Communications, 2025)

Development of a wireless vitamin B2 sensor by using flexible and disposable screen-printed electrode modified with g-C3N4 based ternary composite - Muhammad Zeeshan Asghar; Habibulla Imran; Ali shan; Baoyang Lu; Sooman Lim (Analytica Chimica Acta, 2025)

YOLOv5 Revisited: A Lightweight yet Accurate Framework for Plant Disease Detection in Agricultural Applications - Huria Ali; Muhammad Imran; Saad Irfan Khan; Anees Tariq; Hassan Dawood; Hussain Dawood (Applied Fruit Science, 2025)

Water quality, risk assessment indices, and source apportionment across spatial patterns - Said Muhammad; Nizam Ullah; Wajid Ali; Sehrish Amin; Cem Tokatli; Imran Ud Din; Zafar Iqbal; Umar Farooq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Simulation-based assessment of the impact of conservation tillage and strip intercropping on soil microbial biomass carbon - Sana ur Rehman; Xiaoping Xin; Shahzada Sohail Ijaz; Shroz Fatima; Ayesha Siddiqa; Hayder Bin Khalid; Imran Haider; Rashid Iqbal; Aqib Mahmood; Sajad Hussain; Atta Mohi Ud Din; Taqi Raza; et al. (CATENA, 2025)

From shadow to sustainability: How informality, environmental taxes, and green innovation reshape carbon and biodiversity futures in the G7 countries - Sami Ur Rahman; Imran Ali Khan; Fariha Sami; Javed Hussain; Muhammad Ibrahim Khan (Journal of Environmental Management, 2025)

Prediction of water status during freeze drying with genetic and whale algorithms of machine learning - Shoaib Younas; Muhammad Ahmad; Ukasha Arqam; Muhammad Sajid Manzoor; Xin Wang; Weijie Li; Caiyun Liu; Zeshan Ali; Muhammad Azeem Sabir; Muhammad Imran (International Journal of Refrigeration, 2025)

An effective bi-functional electrocatalyst for electrochemical water splitting using NiCo2O4 nanoparticles decorated with Polypyrrole nanocomposite - Khadija-Tul-Kubra; Faiqa Noreen; Ali Junaid; Atif Nazir; Sehrish Arshad; Komal Bibi; Ayesha Batool; Aleeza Sattar; Aboud Ahmed Awadh Bahajjaj; Sohail Ahmad; Muhammad Shuaib Khand; Syed Imran Abbas Shah (Fuel, 2025)

Cobalt-catalyzed reductive cross-coupling: a review - Shamoon Hassan; Muhammad Bilal; Shehla Khalid; Nasir Rasool; Muhammad Imran; Adnan Ali Shah (Molecular Diversity, 2025)

Impact of Untreated and Wetland Treated Sewage Water Irrigation on Microbiology of Vegetables Grown in Summer and Winter Season - Mahwish Ali; Sanam Islam Khan; Muhammad Imran; Abdul Haleem; Talmeez U. R. Rehman; Safia Ahmed (International Journal of Environmental Research, 2025)

Sulphur Nutrition Improves Plant Growth Performance Against a Specialist Herbivore by Eliciting Phenolic Defense and Nutrient Induction in Rapeseed - Muhammad Wajid Javed; Dilbar Hussain; Muhammad Hasnain; Mubshar Hussain; Imran Ali (Journal of Plant Growth Regulation, 2025)

Spatial distribution, potential health risks, and sources of groundwater contamination in the semi-arid region - Owais Rabbani; Wajid Ali; Ghazanfar A. Khattak; Said Muhammad; Muhammad Nafees; Shahid Iqbal; Imran Ud Din; Ashfaq Ahmad; Umar Farooq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Advancements in metasurfaces for polarization control: A comprehensive survey - Humayun Zubair Khan; Jamal Zafar; Abdul Jabbar; Jalil ur Rehman Kazim; Masood Ur Rehman; Muhammad Ali Imran; Qammer H. Abbasi (Next Research, 2025)

Towards energy efficiency in Pakistan: An analysis of increasing integrated fuel demand using LEAP forecasting and backcasting - Muhammad Shahid; Kafait Ullah; Kashif Imran; Amjad Ali (Fuel, 2025)

Polybenzimidazole-1D interconnected carbon framework decorated with nickel manganese oxide nanoparticles for hybrid supercapacitors - Muhammad Shahid Khan; Hong Meng; Ahmed Shuja; Hasan Ali; Hassan Tariq; Rehan Ullah; Abdullah Saad Alsubaie; Mohd Zahid Ansari; Yaqoob Khan; Imran Murtaza (Chemical Engineering Journal, 2025)

Integrated multidisciplinary analysis of snowfall, freezing risks, and territorial resilience: a case study of the Wilaya of Batna, Algeria - Yahyaoui Habibi; Sami Guellouh; Billel Touati; Abdelwahhab Filali; Zizhan Zhang; Sidao Ni; Risheng Chu; Fouzi Bellalem; Fatima Baala; Houssam Meziani; Muhammad Imran Hafeez Abbasi; Ali Athamena (Mediterranean Geoscience Reviews, 2025)

Managing water deficit in wheat through mulches and irrigation techniques in semi-arid regions - Salman Ahmad; Muhammad Aown Sammar Raza; Muhammad Ali; Rashid Iqbal; Muhammad Usman Aslam; Monika Toleikiene; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Imran Haider; Muhammad Zain; Saltanat Aghayeva; Ozhan Simsek; et al. (Cereal Research Communications, 2025)

Molecular characterization of lumpy skin disease virus in the cattle population of District Lower Chitral, Khyber Pakhtunkhwa, Pakistan - Almas Faryal Nizam; Iram Maqsood; Hanif Ur Rahman; Saira Awaz; Imran Ullah Shah; Muhammad Ijaz Ali; Baitullah Khan; Gul Muhammad; Asima Azam; Ayesha Hidayat (Antonie van Leeuwenhoek, 2025)

Enhanced electrocatalytic OER performance of Ba/CS-CoFe2O4 ternary heterostructure catalyst: Experimental and theoretical insights - Qirat Yameen; Muhammad Ikram; Sawaira Moeen; Muhammad Imran; Anwar Ul-Hamid; Ghafar Ali; Souraya Goumri-Said; Mohammed Benali Kanoun (Chemosphere, 2025)

Exploring soliton and chaotic dynamics in the generalized reaction duffing equation using multiple analytical methods - Azad Ali Sagher; Muhammad Imran Asjad; Md. Mamunur Roshid; Suhad Ali Osman Abdallah (Modeling Earth Systems and Environment, 2025)

Cyto-genotoxic assessment of bisphenol P through expression of DNA damage/repair genes in MDBK cell line - Muhammad Muddassir Ali; Samra Afzal; Maryam Javed; Imran Rashid; Furqan Awan; Asad Ullah; Tanveer Majeed; Hadeer Darwish; Ahmed Noureldeen; Jawaher Albaqami; Khalid Mehmood (In Vitro Cellular & Developmental Biology - Animal, 2025)

In Silico and In Vitro Analysis of Bioactive Compounds from Ficus benghalensis as a Novel Approach to Targeting Brain Abscess Pathogen - Ihtesham Arshad; Maryum Zainab; Ayesha Farooq; Saira Zulfiqar; Anna Ali; Rubina Bibi; Shaista Shafiq; Imran Zafar; Muhammad Mazhar Ayaz; Yahya A. Almutawif; Najeeb Ullah Khan (Cell Biochemistry and Biophysics, 2025)

Marine life as a source of anti-prostate cancer agents: an updated overview (2003–2023) - Amjad Hussain; Ammara Sohail; Muhammad Sajid Hamid Akash; Sarosh Iqbal; Kanwal Rehman; Muhammad Imran; Shoaib Khan; Muhammad Adnan Ayub; Daijie Wang; Dildar Ahmed; Mohammed Hadi Ali Al-Jumaili; Maria Bashir; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Cumulative effect of chronic thermal stress and glyphosate based herbicide exposure on blood parameters and cortisol levels of common carp (Cyprinus carpio) - Imran Khan; Fakhr Ul Islam; Naimat Ullah Khan; Hazrat Ali; Mohammad Attaullah; Muhammad Ikram Khan (Ecotoxicology, 2025)

Correction: Combined Effects of Reduced Tillage and Strip Intercropping on Soil Carbon Sequestration in Semi-Arid Environment - Sana ur Rehman; Shahzada Sohail Ijaz; Atta Mohi Ud Din; Munirah Abdullah Al-Dosary; Muhammad Ansar; Shroz Fatima; Ayesha Siddiqa; Muhammad Nadeem Ashraf; Imran Haider; Muhammad Bilawal Junaid; Muhammad Ali Raza; Haishui Yang (Journal of Soil Science and Plant Nutrition, 2025)

Combined Effects of Reduced Tillage and Strip Intercropping on Soil Carbon Sequestration in Semi-Arid Environment - Sana ur Rehman; Shahzada Sohail Ijaz; Atta Mohi Ud Din; Munirah Abdullah Al-Dosary; Muhammad Ansar; Shroz Fatima; Ayesha Siddiqa; Muhammad Nadeem Ashraf; Imran Haider; Muhammad Bilawal Junaid; Muhammad Ali Raza; Haishui Yang (Journal of Soil Science and Plant Nutrition, 2025)

Comprehensive Genomic, Mutation, Phylogenetic, and Statistical Analysis of the Monkeypox Virus Across Multiple Countries - Imran Zafar; Faheem kanwal; Muhammad Azmat; Ahsanullah Unar; Ijaz Ali; Waqas Yousaf; Qurat ul Ain; Mohd Ashraf Rather; Nemat Ali; Mohammad Rashid Khan; Amandeep Singh Dhanju; Rohit Sharma (Indian Journal of Microbiology, 2025)

Managing anthracnose fruit rot disease in pepper caused by Colletotrichum capsici via potash alum and frankincense essential oil - Mansour M. El-Fawy; Muhammad Imran; Esmat F. Ali; Abeer S. Alqurashi; Ahmed A. Issa; Rabee A. Emam; Mohamed F. Abd El-Mageed; Najeeb M. Almasoudi; Nashwa M. A. Sallam; Kamal A. M. Abo-Elyousr (Journal of Plant Pathology, 2025)

Experimental and first-principles analyses of oxidative defect removal in eco-friendly InP quantum dot synthesis via in situ HF etching - Awais Ali; Faisal Rehman; Tridip Das; Muhammad Imran; Junhyeok Park; Seongkeun Oh; Hanseok Seo; Young Kyun Choi; William A Goddard; Soong Ju Oh (Chemical Engineering Journal, 2025)

Yield gains and resource use advantages driven by legume choice and row ratio in cotton/legume intercropping under arid-irrigated conditions - Muhammad Ali Raza; Atta Mohi Ud Din; Hassan Shehryar Yasin; Hina Gul; Amjad Saeed; Aqib Mehmood; Sana Ur Rehman; Zafar Iqbal; Rashid Iqbal; Noorah Al Kubaisi; Mohamed S. Elshikh; Ghulam Abbas Shah; et al. (Field Crops Research, 2025)

The interplay of p16INK4a and non-coding RNAs: bridging cellular senescence, aging, and cancer - Ashok Kumar Balaraman; Muhammad Afzal; Ehssan Moglad; M. Arockia Babu; G. Padma Priya; Pooja Bansal; Sumit Rajotiya; Benod Kumar Kondapavuluri; Imran Kazmi; Sami I. Alzarea; Kavita Goyal; Haider Ali (Biogerontology, 2025)

Effects of water quality and nitrogen on wheat productivity: Experimental and modelling study using the SALTMED model - Junaid Nawaz Chauhdary; Hong Li; Ragab Ragab; Zawar Hussain; Muhammad Akhlaq; Imran Ali Lakhiar (Irrigation and Drainage, 2025)
The effects of different water qualities and nitrogen doses need to be investigated for wheat growth to determine the optimal management strategy for sustaining wheat production potential to ensure human food security. Therefore, a 2‐year study (2020–2021 to 2021–2022) was conducted on wheat irrigated with different water qualities, including canal water (Ca), tubewell water (Tu) and mixed Ca‐Tu water (Mx), each fertilized with two nitrogen doses, that is, N75 = 75 kgN.ha −1 and N100 = 100 kgN.ha −1 . Ca⨯N100 performed best, with 5.12 t.ha −1 grain yield, 11.60 t.ha −1 biomass, 102.83 cm plant height and 1.32 kg.m −3 water productivity. The best values of the root mean square error (RMSE), normalized root mean square error (NRMSE), coefficient of determination ( R 2 ) and coefficient of residual mass (CRM) were 0.11, 0.12, 0.93 and −0.004, respectively, for calibration and 0.13, 0.15, 0.87 and ±0.01, respectively, for validation of the SALTMED model. The scenario simulation was performed for additional levels of water salinity (electrical conductivity [EC] = 8 and 12 dS.m −1 ) and nitrogen doses (50, 125, 150 and 175 kgN.ha −1 ). The results revealed improvements in wheat grain yield of 107%, 16% and −6% at EC = 8 dS.m −1 and 125%, 31% and 5% at EC = 12 dS.m −1 , while the improvements in biomass were 113%, 22% and −2% at EC = 8 dS.m −1 and 137%, 29% and 8% at EC = 12 dS.m −1 with increasing nitrogen doses from 50–125 kg.ha −1 , 125–150 kg.ha −1 and 150–175 kg.ha −1 , respectively. It is recommended that high‐quality water with the lowest possible EC and nitrogen applications of up to 150 kgN.ha −1 be adopted for wheat production in semi‐arid areas of Punjab, Pakistan.

Effect of human chorionic gonadotropin on oocyte maturation and developmental competence in buffalo - Muhammad Bilal; Muhammad Kamran Ashraf; Talha Ashraf; Muhammad Yaseen; Ali Husnain; Muhammad Bilal Bin Majeed; Muhammad Imran; Burhan E. Azam Rana; Muhammad Hassan Mushtaq; Amjad Riaz (Theriogenology, 2025)

Innovative circular bioeconomy and decarbonization approaches in palm oil waste management: A review - Kai Chen Goh; Tonni Agustiono Kurniawan; G. Abdulkareem AlSultan; Mohd Hafiz Dzarfan Othman; Abdelkader Anouzla; Faissal Aziz; Imran Ali; Joan Cecilia C. Casila; Muhammad Imran Khan; Dongdong Zhang; Choo Wou Onn; Ta Wee Seow; et al. (Process Safety and Environmental Protection, 2025)

Reinforcing urban resilience through sound landfill management: Addressing global climatic challenges with novel solutions - Kai Chen Goh; Tonni Agustiono Kurniawan; Mohd Hafiz Dzarfan Othman; Abdelkader Anouzla; Faissal Aziz; Imran Ali; Joan Cecilia C. Casila; Muhammad Imran Khan; Dongdong Zhang; Wei Dai; Choo Wou Onn; Ta Wee Seow (Process Safety and Environmental Protection, 2025)

Role of artificial intelligence in halal authentication and traceability: A concurrent review - Asad Nawaz; Atka Afzal; Ali Khatibi; Amar Shankar; Heena Madan; Hafiza Sana Faisal; Amna Shahbaz; Ifrah Usman; Nimra Zulfiqar; Farhan Saeed; Aftab Ahmed; Ali Imran; et al. (Food Control, 2025)

Expression and characterization of the immunogenicity of rec-gp45 of Babesia bigemina using cattle - Zia-Ul-Rehman; Sarfraz-ur-Rahman; Kamran Ashraf; Muhammad Suleman; Sikandar Ali; Muhammad Imran Rashid (Tropical Animal Health and Production, 2025)

Impacts of Conservation Tillage on Agricultural Land Development: A Review - Xue Liang; Sana Ur Rehman; Wang Zhiqi; Muhammad Ali Raza; Imran Haider; Muhammad Hayder Bin Khalid; Amjad Saeed; Zafar Iqbal; Shroz Fatima; Ayesha Siddiqa; Muhammad Ansar; Shahzada Sohail Ijaz; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Implications of nociceptor receptors and immune modulation: emerging therapeutic targets for autoimmune diseases - Syeda Asloob Fatima; Bushra Akhtar; Ali Sharif; Muhammad Imran Khan; Muhammad Shahid; Fozia Anjum; Fatma Hussain; Aisha Mobashar; Maham Ashraf (Inflammopharmacology, 2025)

Development of a dispersive liquid–liquid microextraction technique for ultra-sensitive detection of gold in environmental samples using atomic absorption spectrometry - Waheed Ali Soomro; Muhammad Yar Khuhawar; Taj Muhammad Jahangir; Muhammad Farooque Lanjwani; Zulfiqar Ali Bhatti; Rafi-u-Zaman Brohi; Imran Khan Rind (Environmental Monitoring and Assessment, 2025)

T-2 mycotoxin: From occurrence and toxicokinetics to recent advances in aptasensor-based detection strategies and future perspectives for enhanced food safety - Ali Raza; Sobia Niazi; Muhammad Shoaib; Imran Mahmood Khan; Faizan Ul Haq; Khubaib Ali; Ibrahim Khan; Yin Zhang; Zhouping Wang (Trends in Food Science & Technology, 2025)

Maximizing heavy metal removal and precious metal recovery with innovative biowaste-derived biosorbents and biochar - Behzad Murtaza; Roshina Arshad; Moon Kinza; Jianxu Wang; Muhammad Shahid; Muhammad Imran; Noor S. Shah; Qasim Ali; Jibran Iqbal; Changseok Han (Process Safety and Environmental Protection, 2025)

Photovoltaic module efficiency enhancement system by novel cooling techniques: Effect of phase change material and fins - Saad Saeed; Abid Hussain; Imran Ali; Hanzla Shahid; Muhammad Anwar; Hafiz Muhammad Ali (Process Safety and Environmental Protection, 2025)

Catalytic-assisted remediation and phytotoxicity evaluations of organic pollutants in the presence of metal-doped Bi2O3-based NPs catalyst - Farah Fahim; Muhammad Imran; Muhammad Ramzan; Zarish Nazeer; Awais Ali; Haﬁz M.N. Iqbal (Journal of Environmental Management, 2025)

Xylooligosaccharides: A comprehensive review of production, purification, characterization, and quantification - Khubaib Ali; Nadia Niaz; Muhammad Waseem; Waqas Ashraf; Mudassar Hussain; Muhammad Umair Khalid; Assam Bin Tahir; Ali Raza; Imran Mahmood Khan (Food Research International, 2025)

Amine-functionalized organically modified silica for the effective adsorption of Chlorpyrifos and Triazophos Residues from Orange juice - Muhammad Hayat; Suryyia Manzoor; Nadeem Raza; Hina Raza; Ayesha Javid; Zeeshan Ali; Muhammad Imran Khan; Faisal K. Algethami; Najla AlMasoud; Taghrid S. Alomar (Food Chemistry, 2025)

Insights into the dynamics of biochemical profile and relative gene expression of cucumber fruits associated with Fusarium spoilage - Muhammad Imran; Hanan A. Khalifa; Zhongke Sun; Muhammad Saqib Bilal; Mohamed Hassan Abd El-Wahed; Kamal A. M. Abo-Elyousr; Esmat F. Ali; Chengwei Li (Journal of Plant Diseases and Protection, 2025)

Insight into insecticide resistance mechanism and eco-friendly approaches for the management of olive fruit fly, Bactrocera oleae Rossi: a review - Ansa Majeed; Muhammad Tariq Rasheed; Javairia Akram; Noreen Shahzadi; Mehvish Kousar; Imran Bodlah; Javaid Iqbal; Inzamam Ul Haq; Yasir Munir; Junaid Ali Siddiqui (Journal of Plant Diseases and Protection, 2025)

Effect of plastic fibers on OPC-based concrete in circular economy - Shehroze Ali; Suliman Khan; Muhammad Imran; Faizan Ali; Mohsin Nawaz (Innovative Infrastructure Solutions, 2025)

Targeting senescence and GATA4 in age-related cardiovascular disease: a comprehensive approach - Mohd Imran; Abdulmalik S. A. Altamimi; Muhammad Afzal; M. Arockia Babu; Kavita Goyal; Suhas Ballal; Pawan Sharma; Fadiyah Jadid Alanazi; Abeer Nuwayfi Alruwaili; Nouf Afit Aldhafeeri; Haider Ali (Biogerontology, 2025)

Innovative transformation of palm oil biomass waste into sustainable biofuel: Technological breakthroughs and future prospects - Tonni Agustiono Kurniawan; Mehwish Ali; Ayesha Mohyuddin; Ahtisham Haider; Mohd Hafiz Dzarfan Othman; Abdelkader Anouzla; Hui Hwang Goh; Dongdong Zhang; Wei Dai; Faissal Aziz; Muhammad Imran Khan; Imran Ali; et al. (Process Safety and Environmental Protection, 2025)

Titanium dioxide nanoparticles seed priming as a remedy for nickel-induced stress in maize through antioxidant enhancement and ultrastructural optimization - Muhammad Rehman; Abdul Salam; Bahar Ali; Irshan Ahmad; Muhammad Haseeb Javaid; Zulqarnain Haider; Raheel Munir; Muhammad Umair Yasin; Imran Ali; Chunyan Yang; Sajid Muhammad; Yinbo Gan (Journal of Environmental Management, 2025)

Developing Ag3VO4@ZnO electrode material for efficient oxygen evolution reaction showcasing its potential for sustainable energy applications - Ali Junaid; Faiqa Noreen; Abdus Sami; Karam Jabbour; Khadija Bibi; Muhammad Ammar Hassan Shah; Nigarish Bano; Muhammad Shuaib Khan; Asma A. Alothman; Syed Imran Abbas Shah (Fuel, 2025)

Olive oil and castor oil-based self-nanoemulsifying drug delivery system of flurbiprofen can relieve peripheral pain and inflammation through reduction of oxidative stress and inflammatory biomarkers: a comprehensive formulation and pharmacological insights - Mazaghul Basar; Muhammad Imran Khan; Muhammad Furqan Akhtar; Fareeha Anwar; Ammara Saleem; Asadullah Madni; Zulcaif Ahmad; Ali Sharif; Bushra Akhtar; Uzma Shakoor; Aslam Khan (Inflammopharmacology, 2025)

Zinc-lysine and iron-lysine mitigate chromium toxicity in pearl millet (Pennisetum glaucum) through modulating photosynthetic and antioxidant system and inhibiting chromium uptake and translocation - Zaryab Ali Abbass; Maryam Zahra; Habib Ali; Muhammad Javed; Imran Mahmood; Mavadat Hussain Alvi; Alishba Waheed; Sadam Hussain; Sachin Kumar (Environmental Science and Pollution Research, 2024)

Synergistic effect of biochar and intercropping on lead phytoavailability in the rhizosphere of a vegetable-grass system - Muhammad Rizwan; Ghulam Murtaza; Zeeshan Ahmed; Qimei Lin; Xuejiao Chen; Imran Khan; Hamada Abdelrahman; Vasileios Antoniadis; Esmat F. Ali; Sang Soo Lee; Lijian Leng; Sabry M. Shaheen; et al. (Science of The Total Environment, 2024)

Potentially harmful elements contamination, risk assessment, and their bioaccumulation in food crops - Imran Ud Din; Said Muhammad; Cem Tokatli; Inayat ur Rehman; Wajid Ali; Mohammed Rafi Shaik; Mohamed E. Assal; Ayaz Ul Haq; Shaik Althaf Hussain (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Chemical modification of Pinus walliichiana sawdust: Application in membrane system for efficient purification of groundwater containing Cd(II) and Ni(II) - Muhammad Imran Irfan; Mahnoor Sadiq; Lubna Zohra; Abu Bakar Siddique; Muhammad Yousaf; Madiha Rubab; Kishwar Urooj; Ambreen Aziz; Hira Ali; Mehreen Fatima; Hatem M.A. Amin; Hassan A. Alhazmi; et al. (Journal of Water Process Engineering, 2024)

Efficient removal of perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS) from aqueous solution using modified biochar: Preparation, performance, and mechanistic insights - Waqas Niaz; Dahai Zhang; Zia Ahmad; Nan Shen; Waqas Haider; Imran Ali; Muhammad Usman; Abdul Majid; Sheikh Fahad Javaid; Muhammad Ahsan Amjed; Xianguo Li (Journal of Environmental Chemical Engineering, 2024)

Unveiling genetic variants: Tetra-primer ARMS-PCR diagnosis and structural insights into BLAD, BC, and DUMPS in Pakistani cattle herds - Iram Ilyas; Fakhar un Nisa; Muhammad Basil Ali; Fazeela Arshad; Najida Irfan; Muhammad Asif; Imran Amin (Molecular Biology Reports, 2024)

Deciphering the differential expression patterns of yield-related negative regulators in hexaploid wheat cultivars and hybrids at different growth stages - Muhammad Jawad Akbar Awan; Muhammad Awais Farooq; Rubab Zahra Naqvi; Umer Karamat; Sayyad Ali Raza Bukhari; Muhammad Abu Bakar Waqas; Muhammad Arslan Mahmood; Muhammad Ismail Buzdar; Awais Rasheed; Imran Amin; Nasir A. Saeed; Shahid Mansoor (Molecular Biology Reports, 2024)

The interplay of PTEN and AKT nexus in breast cancer: a molecular perspective - Anum Kamal; Ali Raza Awan; Masood Rabbani; Hammad Raza Sheikh; Muhammad Tayyab; Sehrish Firyal; Imran H. Khan; Muhammad Wasim (Molecular Biology Reports, 2024)

Exome sequencing in four families with neurodevelopmental disorders: genotype–phenotype correlation and identification of novel disease-causing variants in VPS13B and RELN - Tehseen Ullah Khan Afridi; Ambrin Fatima; Humayoon Shafique Satti; Zaineb Akram; Imran Khan Yousafzai; Wajahat Bin Naeem; Nasreen Fatima; Asmat Ali; Zafar Iqbal; Ayaz Khan; Muhammad Shahzad; Chunyu Liu; et al. (Molecular Genetics and Genomics, 2024)

Effectiveness of biochar and wood vinegar from guava trees in controlling Fusarium verticillioides and enhancing growth and anatomical traits of maize (Zea mays L.) - Mansour M. El-Fawy; Ayman S. Saeed; Mohamed K. Abou-Shlell; Mahmoud A. Soliman; Esmat F. Ali; Ahmed A. Issa; Kamal A. M. Abo-Elyousr; Muhammad Imran; Asmaa S. El-Nagar (Journal of Plant Diseases and Protection, 2024)

Nitrogen and carbohydrate metabolisms are key factors in maize (Zea mays L.) germination under chromium-induced ROS - Muhammad Imran Atta; Syeda Sadaf Zehra; Zhihang Zhuo; Habib Ali; Malik Waseem Abbas; Syed Naveed Abbas; Sadia Sarwar; Fatima Muneer; Irfan Ahmad; Danpping Xu; Hasham S. Almoallim; Mohammad Javed Ansari (Journal of Plant Diseases and Protection, 2024)

Correction: Determination of Toxic Elements in Cannabinoid and Opioid Drugs and Their Impact on Addicts’ Health: A Comparative Study - Ahsanullah Unar; Oan Muhammad Sahito; Laila Alsawalha; Hassan Imran Afridi; Farid Shokry Ataya; Muhammad Sohail Bashir; Dalia Fouad; Farah Naz Talpur; Naveed Ali (Biological Trace Element Research, 2024)

Determination of Toxic Elements in Cannabinoid and Opioid Drugs and Their Impact on Addicts’ Health: A Comparative Study - Ahsanullah Unar; Oan Muhammad Sahito; Laila Alsawalha; Hassan Imran Afridi; Farid Shokry Ataya; Muhammad Sohail Bashir; Dalia Fouad; Farah Naz Talpur; Naveed Ali (Biological Trace Element Research, 2024)

Therapeutic Potential of Green Synthesized Silver Nanoparticles for Promoting Wound-Healing Process in Diabetic Mice - Riffat Iqbal; Amna Asghar; Arslan Habib; Shaista Ali; Sadaf Zahra; Muhammad Imran Hussain; Ahmad Bilal Ahsan; Yulai Liang (Biological Trace Element Research, 2024)

Polygonum bistorta Linn. as a green source for synthesis of biocompatible selenium nanoparticles with potent antimicrobial and antioxidant properties - Hafiz Abdul Haseeb; Muhammad Aslam Khan; Hassam Rasheed; Muhammad Usman Zahid; Thu Dung Doan; Muhammad Aamir Ramzan Siddique; Uzair Ahmad; Syed Ali Imran Bokhari (BioMetals, 2024)

Dietary Chlorella vulgaris mitigates aflatoxin B1 toxicity in broiler chicken: Toxicopathological, hematobiochemical and immunological perspectives - Aisha Khatoon; Aneela Amin; Sana Majeed; Shafia Tehseen Gul; Muhammad Imran Arshad; Muhammad Kashif Saleemi; Ashiq Ali; Rao Zahid Abbas; Sheraz Ahmad Bhatti (Toxicon, 2024)

Nutritional and medicinal plants as potential sources of enzyme inhibitors toward the bioactive functional foods: an updated review - Hammad Saleem; Anam Yaqub; Rabiya Rafique; Tahir Ali Chohan; Durr-e-Shahwar Malik; Muhammad Imran Tousif; Umair Khurshid; Nafees Ahemad; Ramasamy Ramasubburayan; Kannan RR Rengasamy (Critical Reviews in Food Science and Nutrition, 2024)

Greenly synthesized zinc oxide nanoparticles: An efficient, cost-effective catalyst for dehydrogenation of formic acid and with improved antioxidant and phyto-toxic properties - Sami Ullah; Muhammad Shaban; Abu Bakar Siddique; Anam Zulfiqar; Naveed Shahzad Lali; Muhammad Naeem-ul-Hassan; Muhammad Imran Irfan; Muhammad Sher; Muhammad Fayyaz ur Rehman; Ali Hanbashi; Fahad Y. Sabei; Hatem M.A. Amin; et al. (Journal of Environmental Chemical Engineering, 2024)

Editing microbes to mitigate enteric methane emissions in livestock - Faheem Ahmed Khan; Azhar Ali; Di Wu; Chunjie Huang; Hamza Zulfiqar; Muhammad Ali; Bilal Ahmed; Muhammad Rizwan Yousaf; Ezi Masdia Putri; Windu Negara; Muhammad Imran; Nuruliarizki Shinta Pandupuspitasari (World Journal of Microbiology and Biotechnology, 2024)

Spatiotemporal analysis and clinico-epidemiological study for seroprevalence of canine leptospirosis - Muhammad Imran; Muhammad Hassan Saleem; Aneela Zameer Durrani; Ali Ahmad Sheikh (Veterinary Research Communications, 2024)

Flaxseed mucilage—a green additive for the enhancement of water-based mud system characteristics - Faiza Kanwal; Shaine Mohammadali Lalji; Syed Imran Ali; Muneeb Burney; Muhammad Ovais Tariq; Leena Hasan Ahmed; Umer Ahmed Khan; Aashan Sheikh; Muhammad Salman (Arabian Journal of Geosciences, 2024)

Antioxidant dimension and potential as bacterial growth inhibitors in crude extracts of two Artemisia species (Artemisia indica Willd. and Artemisia maritima L.) from Gilgit-Baltistan region, Pakistan - Hassam Rasheed; Adil Hussain; Muhammad Aslam Khan; Mujtaba Hassan; Syed Ali Imran Bokhari (Vegetos, 2024)

One stone two birds: Endophytes alleviating trace elements accumulation and suppressing soilborne pathogen by stimulating plant growth, photosynthetic potential and defense related gene expression - Muhammad Imran; Zhongke Sun; Kamal A.M Abo-Elyousr; Haider Ali; Munirah F. Aldayel; Chengwei Li (Journal of Hazardous Materials, 2024)

Molecular detection of Coxiella burnetii in ticks infesting wild and domestic animals in the Eastern region of Punjab, Pakistan - Freeha Amin; Shahzad Ali; Muhammad Imran; Nora G. Cleary; Michael E. von Fricken; Iahtasham Khan (Tropical Animal Health and Production, 2024)

Alleviating Drought Stress in Strawberry Plants: Unraveling the Role of Paclobutrazol as a Growth Regulator and Reducer of Oxidative Stress Induced by Reactive Oxygen and Carbonyl Species - Khansa Saleem; Muhammad Ahsan Asghar; Ali Raza; Kaiwen Pan; Abd Ullah; Hafiz Hassan Javed; Mahmoud F. Seleiman; Shakeel Imran; Sajid Mehmood Nadeem; Khurram Shehzad Khan; Junbo Du; Fei Xu; et al. (Journal of Plant Growth Regulation, 2024)

Zinc solubilizing bacteria synergize the effect of zinc sulfate on growth, yield and grain zinc content of rice (Oryza sativa) - Muhammad Shakeel; Fauzia Yusuf Hafeez; Imran Riaz Malik; Abdur Rauf; Farooq Jan; Ikramullah Khan; Iram Ijaz; Mohamed Farouk Elsadek; Muhammad Ajmal Ali; Kamran Rashid; Muhammad Muzammal; Muhammad Munir; et al. (Cereal Research Communications, 2024)
Zinc solubilizing bacteria inhabiting root endosphere possesses great potential to enhance plant yield by solubilizing the nutrients. The potential of Zn solubilizing bacteria Bacillus sp. SH-10 and Bacillus cereus SH-17 to improve yield and grain zinc content of rice was investigated under different regimes of individual and co-inoculation in the presence and absence of chemical fertilizer zinc sulfate (ZnSO 4 ). The strains were applied to the rice varieties basmati 385 and super basmati under field conditions for two consecutive years. A significantly improved growth of rice plants, such as plant height (102–118 cm), number of tillers per plant (8.5–11.5), chlorophyll content (29.5–35.1), zinc requiring enzymes, i.e., superoxide dismutase (396–570 per gram fresh weight (g −1 FW)), carbonic anhydrase activity (CA) (10–15.06 U g −1 FW) and grain yield (3.0–3.8 tons ha −1 ), was observed in the plants inoculated with Bacillus sp. in the presence of chemical fertilizer (ZnSO 4 ). Consortium of zinc solubilizing bacteria also caused higher grain Zn content (25.0–30.5 mg kg −1 ) of the rice varieties basmati 385 and super basmati as compared to that of un-inoculated plants. Hence, it can be concluded that Zn solubilizing bacteria has immense potential to be used as agricultural crop inoculants as they synergize the effect of chemical Zn, increase yield and improve the nutritional value of crops.

Biochemical and nutritional analysis of seaweed (Iyengaria stellata) and its therapeutic significance, using antioxidant, antimicrobial, and hypoglycemic activities - Muhammad Imran; Arshad Iqbal; Arwa Abdulkreem AL-Huqail; Suliman Mohammed Suliman Alghanem; Syed Lal Badshah; Saad Alghamdi; Mazen Almehmadi; Uthman Balgith Algopishi; Baber Ali; Saima Sohni; Muhammad Ammar Javed; Doaa Bahaa Eldin Darwish (South African Journal of Botany, 2024)

Insight into mechanism of excellent visible-light photocatalytic activity of CuO/MgO/ZnO nanocomposite for advanced solution of environmental remediation - Muhammad Imran; Mohsin Raza; Hadia Noor; Sadia Muniza Faraz; Ali Raza; Umar Farooq; Mohammad Ehtisham Khan; Syed Kashif Ali; Omer Y. Bakather; Wahid Ali; Abdullateef H. Bashiri; Waleed Zakri (Chemosphere, 2024)

Risk identification of salts and heavy metals in water by multivariate statistical techniques and GIS based interpolation: A case study of Saeedabad, Sindh, Pakistan - Imran Khan Rind; Muhammad Yar Khuhawar; Taj Muhammad Jahangir; Najma Memon; Ahsan Habib; Muhammad Farooque Lanjwani; Waheed Ali Soomro; Ghamshan Suther; Wenbin Liu (Regional Studies in Marine Science, 2024)

Exploiting and Enhancing the Heat Transport Rate of MoS2-Ag/EO Hybrid Nanofluid Flow via a Stretching Cylinder using Extended Yamada–Ota and Xue Models - Nahid Fatima; Ali Basem; Umar Farooq; Muhammad Imran; Haihu Liu; Taseer Muhammad; Sobia Noreen; Hassan Waqas (Journal of Fluorescence, 2024)

Impact of cement waste on soil fertility and crop productivity: a serious concern for food security - Junaid Iqbal; Muhammad Jamal Khan; Muhammad Hafeez; Junaid Ali Siddiqui; Muhammad Fahad; Bahar Ali; Muhammad Imran; Aqeel Ahmad; Shah Fahad (Environmental Science and Pollution Research, 2024)

Modern ecofriendly approach for extraction of luteolin natural dye from weld for silk fabric and wool yarn dyeing - Syed Ali Raza Naqvi; Kaif ul-Wara; Shahid Adeel; Rony Mia; Mozhgan Hosseinnezhad; Luqman Jameel Rather; Muhammad Imran (Sustainable Chemistry and Pharmacy, 2024)

RETRACTED: Almond shell-derived biochar decreased toxic metals bioavailability and uptake by tomato and enhanced the antioxidant system and microbial community - Muhammad Imran Ghani; Mohammad Abass Ahanger; Tanveer Ali Sial; Sajjad Haider; Junaid Ali Siddique; Ruidong Fan; Yanjiang Liu; Esmat F. Ali; Manish Kumar; Xing Yang; Jörg Rinklebe; Xiaoyulong Chen; et al. (Science of The Total Environment, 2024)

Insights into the involvement of male Hyalomma anatolicum ticks in transmitting Anaplasma marginale, lumpy skin disease virus and Theileria annulata - Sikandar Ali; Abdullah Saghir Ahmad; Kamran Ashraf; Jawaria Ali Khan; Muhammad Imran Rashid (Tropical Animal Health and Production, 2024)

Morpho-Physiological and Enzymatic Responses of Zinnia (Zinnia elegans L.) to Different Metal Hoarded Wastewaters - Muhammad Ahsan; Adnan Younis; Muhammad Raheel; Imran Khalid; Hafiz Tassawar Abbas; Waqas Ashraf; Adil Mihoub; Emanuele Radicetti; Muhammad Farhan Saeed; Sajjad Ali; Mohammad Valipour; Aftab Jamal (Journal of Soil Science and Plant Nutrition, 2024)

Integrating FinTech with Industry 4.0 for sustainable mineral resource management: Exploring the interplay of technology, regulation, and economic dynamics - Imran Khan; Inayat Khan; Rana Muhammad Adnan Ikram; Mohammad Ajmal Ali (Resources Policy, 2024)

The impact of formaldehyde exposure on lung inflammatory disorders: Insights into asthma, bronchitis, and pulmonary fibrosis - Asif Ahmad Bhat; Muhammad Afzal; Ahsas Goyal; Gaurav Gupta; Riya Thapa; Waleed Hassan almalki; Imran Kazmi; Sami I. Alzarea; Moyad Shahwan; Keshav Raj Paudel; Haider Ali; Dipak Sahu; et al. (Chemico-Biological Interactions, 2024)

Spatial distribution and potential health risk assessment for fluoride and nitrate via water consumption in Pakistan - Imran Ud Din; Wajid Ali; Said Muhammad; Mohammed Rafi Shaik; Baji Shaik; Inayat ur Rehman; Cem Tokatli (Journal of Geochemical Exploration, 2024)

Highly selective and effective oxidation of 5-hydroxymethylfurfural by Co-Ni based electrodeposited bimetallic oxide nanostructures - Ghazala Nawaz; Mahnoor Fatima; Zahoor Ahmad; Khurram Saleem Joya; Mohammed Ali Assiri; Syed Imran Abbas Shah; Farhat Yasmeen; Muhammad Naeem Khan (Fuel, 2024)

Synthesis of novel nonsteroidal anti-inflammatory galloyl β-sitosterol-loaded lignin-capped Ag-based drug - Sana Malik; Batool Fatima; Dilshad Hussain; Muhammad Imran; Tahir Ali Chohan; Muhammad Saqib Khan; Saadat Majeed; Muhammad Najam-ul-Haq (Inflammopharmacology, 2024)

Correction to: Domperidone nanocrystals with boosted oral bioavailability: fabrication, evaluation and molecular insight into the polymer-domperidone nanocrystal interaction - Stalielson Tatenda Ndlovu; Naseem Ullah; Shahzeb Khan; Pritika Ramharack; Mahmoud Soliman; Marcel de Matas; Muhammad Shahid; Muhammad Sohail; Muhammad Imran; Syed Wadood Ali Shah; Zahid Hussain (Drug Delivery and Translational Research, 2024)

Predicting asphaltene adsorption on Fe3O4 nanoparticle using machine learning algorithms - Syed Imran Ali; Shaine Mohammadali Lalji; Usama Ahsan; Syed Muhammad Ali; Yassar Kamal Zia; Sajid Hussain; Muneeb Burney; Muhammad Qasim; Zeeshan Ahmad Arfeen (Arabian Journal of Geosciences, 2024)

Synergistic effect of Paclobutrazol and silver nanoparticles (AgNPs) control the pod shattering in canola (Brassica napus L.) via physiological interferences: a mechanistic overview - Habib Ali; Imran Mahmood; Ghulam Qadir; Naveed Iqbal Raja; Fozia Abasi; Mukhtar Ahmed; Muhammad Faizan Ali; Husnain Jawad; Jarosław Proćków (Acta Physiologiae Plantarum, 2024)

Examining the natural resources-ecological degradation nexus: The role of energy innovation and human capital in BRICST nations - Xiaoya Gu; Imran Ali Baig; Muhammad Shoaib; Shuo Zhang (Resources Policy, 2024)

Empirical analysis of cost-effective and equitable solid waste management systems: Environmental and economic perspectives - Asif Iqbal; Abdullah Yasar; Abdul-Sattar Nizami; Rafia Haider; Imran Ali Sultan; Aman Anwer Kedwaii; Muhammad Murtaza Chaudhary; Muhammad Hassan Javed; Anees Ahmad; Khadija Sajid; Muhammad Naqvi; Muhammad Usman Ghori (Environmental Research, 2024)

FinTech-powered integration: Navigating the static and dynamic connectedness between GCC equity markets and renewable energy cryptocurrencies - Shoaib Ali; Muhammad Naveed; Manel Youssef; Imran Yousaf (Resources Policy, 2024)

Marine Streptomyces sp. PGC 39: A treasure trove of new antimicrobial agents, macrolidycin, and pyrachlomycin - Rabbia Ahmad; Muhammad Imran Tousif; Mamona Nazir; Asma Yaqoob; Syed Adnan Ali Shah; Gokhan Zengin; Abdullahi Ibrahim Uba; Shabbir Muhammad (Food Bioscience, 2024)

Multifunctional role of nanoparticles for the diagnosis and therapeutics of cardiovascular diseases - Ihtesham Arshad; Ayesha Kanwal; Imran Zafar; Ahsanullah Unar; Hanane Mouada; Iashia Tur Razia; Safina Arif; Muhammad Ahsan; Mohammad Amjad Kamal; Summya Rashid; Khalid Ali Khan; Rohit Sharma (Environmental Research, 2024)

Heavy metal(loid)s contamination and ecotoxicological hazards in coal, dust, and soil adjacent to coal mining operations, Northwest Pakistan - Imran Ud Din; Said Muhammad; Shah Faisal; Inayat ur Rehman; Wajid Ali (Journal of Geochemical Exploration, 2024)

Recent development in advanced photocatalytic materials for oxidative removal of bisphenol - Hubdar Ali Maitlo; ZhongZheng Hu; Imran Ali; Ghulamullah Maitlo; Dae-Hwan Lim; Muhammad Naveed Afridi; Minghua Zhou (Journal of Cleaner Production, 2024)

Spherical Fe2O3 nanoparticles inhibit the production of aflatoxins (B1 and B2) and regulate total soluble solids and titratable acidity of peach fruit - Mahnoor Akbar; Naeem Ali; Muhammad Imran; Arshad Hussain; Syed Waqas Hassan; Urooj Haroon; Asif Kamal; Farhana; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (International Journal of Food Microbiology, 2024)

Modelling of debris-flow susceptibility and propagation: a case study from Northwest Himalaya - Hamza Daud; Javed Iqbal Tanoli; Sardar Muhammad Asif; Muhammad Qasim; Muhammad Ali; Junaid Khan; Zahid Imran Bhatti; Ishtiaq Ahmad Khan Jadoon (Journal of Mountain Science, 2024)

Biochemical profile of Vaucheria karachiensis and evaluation of its nutritional, antioxidant, antimicrobial, and hypoglycemic potentials - Arshad Iqbal; Muhammad Imran; Syed Lal Badshah; Ashwag Shami; Baber Ali; Zamarud Shah; Muhammad Ayaz; Abdulrahman Alasmari; Marzough Aziz Albalawi; Amin A. Al-Doaiss; Majed A. Bajaber; Sezai Ercisli (Algal Research, 2024)

Water quality index and geographic information system to assess the groundwater quality of taluka Matiari, Sindh, Pakistan - Imran Khan Rind; Muhammad Yar Khuhawar; Taj Muhammad Jahangir; Najma Memon; Muhammad Farooque Lanjwani; Waheed Ali Soomro (Arabian Journal of Geosciences, 2024)

Modulation of metal transporters, oxidative stress and cell abnormalities by synergistic application of silicon and titanium oxide nanoparticles: A strategy for cadmium tolerance in rice - Mingyu Lai; Fozia Ghouri; Samreen Sarwar; Sarah Owdah Alomrani; Muhammad Riaz; Fasih Ullah Haider; Jingwen Liu; Muhammad Imran; Shafaqat Ali; Xiangdong Liu; Muhammad Qasim Shahid (Chemosphere, 2023)

Genome wide identification and expression profiling of PYL genes in barley - Ali Shahzad; Muhammad Shahzad; Muhammad Imran; Hameed Gul; Shareef Gul (Plant Gene, 2023)

Exploring the hidden treasures of Nitella hyalina: a comprehensive study on its biological compounds, nutritional profile, and unveiling its antimicrobial, antioxidative, and hypoglycemic properties - Muhammad Imran; Arshad Iqbal; Syed Lal Badshah; Imtiaz Ahmad; Ashwag Shami; Baber Ali; Fatema Suliman Alatawi; Mohsen Suliman Alatawi; Yasser S. Mostafa; Saad A. Alamri; Ahlam A. Alalwiat; Majed A. Bajaber (World Journal of Microbiology and Biotechnology, 2023)

Sequence variants in different genes underlying Bardet-Biedl syndrome in four consanguineous families - Amjad Ali; Abdullah; Muhammad Bilal; Emily Kathryn Mis; Saquib Ali Lakhani; Wasim Ahmad; Imran Ullah (Molecular Biology Reports, 2023)

Field response and molecular screening of European wheat germplasm against powdery mildew at the Himalayan region of Pakistan - Aamir Iqbal; Zia Ur Rehman; Muhammad Rameez Khan; Amir Muhammad Khan; Shahid Ullah Khan; Muhammad Arif; Javaid Iqbal; Mujeeb Ur Rehman; Minhaj Ali; Muhammad Qasim; Imran Ali; Zakir Hussain Facho; et al. (Journal of Applied Genetics, 2023)

Production, purification, and characterization of p-diphenol oxidase (PDO) enzyme from lignolytic fungal isolate Schizophyllum commune MF-O5 - Muhammad Faheem; Syed Ali Imran Bokhari; Muhammad Arshad Malik; Bashir Ahmad; Muhammad Riaz; Nafeesa Zahid; Adil Hussain; Abdul Ghani; Hanif Ullah; Waseem Shah; Rashid Mehmood; Khurshid Ahmad; et al. (Folia Microbiologica, 2023)

Industrial wastewater irrigation increased higher heavy metals uptake and expansins, metacaspases, and cystatin genes expression in Parthenium and maize - Kinza Penzy; Said Muhammad; Muhammad Shahzad; Imran Hussain; Sabaz Ali Khan; Arshad Mehmood Abbasi; Imtiaz Khan; Rafiq Ahmad (Environmental Monitoring and Assessment, 2023)

Comparison of As removal efficiency and health risks from aqueous solution using as-synthesized Fe0 and Cu0: modelling, kinetics and reusability - Behzad Murtaza; Asad Ali; Muhammad Imran; Abdullah A. Al-Kahtani; Zeid A. ALOthman; Natasha Natasha; Muhammad Shahid; Noor S. Shah; Muhammad Asif Naeem; Sajjad Ahmad; Ghulam Murtaza (Environmental Geochemistry and Health, 2023)

A decline in snow cover area of Passu and Ghulkin valleys between 1995 and 2022 - Imran Hussain; Mumtaz Ali; Sher Muhammad; Wajid Hassan; Salar Ali; Zakir Hussain; Syed Hammad Ali; Shaukat Ali; Muhammad Younis Khan (Journal of Mountain Science, 2023)

A bacterial consortium and L-tryptophan boosted glyphosate removal, mungbean growth and physiology in contaminated soil - Qammar Farooq; Muhammad Imran Khan; Muhammad Hayder Ali; Safdar Bashir; Muhammad Azam; Rashad Qadri; Basharat Ali; Muhammad Dawood; Muhammad Iftikhar Hussain (Arabian Journal of Geosciences, 2023)

Enhancement in photocatalytic selectivity of TiO2-based nano-catalyst through molecular imprinting technology - Abdul Wahab; Muhammad Ali Minhas; Huma Shaikh; Hua-Ming Xiao; Muhammad Imran Malik (Environmental Science and Pollution Research, 2023)

Annual effective dose estimation of radon in drinking water sources of Nizampur basin, North Western Pakistan - Jehangir Ijaz; Wajid Ali; Said Muhammad; Hayat Ullah; Danish Ather; Imran Ud Din (Isotopes in Environmental and Health Studies, 2023)

Alleviation of cadmium toxicity and fortification of zinc in wheat cultivars cultivated in Cd contaminated soil - Khadim Dawar; Ishaq Ahmad Mian; Shadman Khan; Anwar Zaman; Subhan Danish; Ke Liu; Matthew Tom Harrison; Shah Saud; Shah Hassan; Taufiq Nawaz; Imran Khan; Haitao Liu; et al. (South African Journal of Botany, 2023)

Impacts and mechanism of biodegradable microplastics on lake sediment properties, bacterial dynamics, and greenhouse gasses emissions - Zequn Fan; Cuiling Jiang; Tahir Muhammad; Imran Ali; Yakun Feng; Lei Sun; Hui Geng (Science of The Total Environment, 2023)

Tackling microplastics pollution in global environment through integration of applied technology, policy instruments, and legislation - Tonni Agustiono Kurniawan; Ahtisham Haider; Ayesha Mohyuddin; Rida Fatima; Muhammad Salman; Anila Shaheen; Hafiz Muhammad Ahmad; Hussein E. Al-Hazmi; Mohd Hafiz Dzarfan Othman; Faissal Aziz; Abdelkader Anouzla; Imran Ali (Journal of Environmental Management, 2023)

A renewable and sustainable framework for clean fuel towards circular economy for solid waste generation in leather tanneries - Arshid Mahmood Ali; Arslan Khan; Muhammad Shahbaz; Muhammad Imtiaz Rashid; Muhammad Imran; Khurram Shahzad; Aishah Binti Mahpudz (Fuel, 2023)

CIMCA: Infusing computational intelligence in multi-criteria analysis to assess groundwater potential for recharge - Rashed Uz Zzaman; Muhammad Ali Nayeem; Sara Nowreen; Imran Hossain Newton; AKM Saiful Islam; Anwar Zahid; M. Sohel Rahman (Environmental Modelling & Software, 2023)

Elucidating growth and biochemical characteristics of rice seedlings under stress from chromium VI salt and nanoparticles - Maryam Noor; Arif Ullah; Muhammad Israr Khan; Irum Raza; Muhammad Iqbal; Abdul Aziz; Gil Won Kim; Nadia Taimur; Azizullah Azizullah; Imran Ali; Pil Joo Kim (Environmental Science and Pollution Research, 2023)

Modifying engineered nanomaterials to produce next generation agents for environmental remediation - Muhammad Arslan Ahmad; Muhammad Adeel; Noman Shakoor; Rabia Javed; Muhammad Ishfaq; Yutao Peng; Muhammad Zain; Imran Azeem; Ilyas Ali; Muhammad Usman; Zihao Wu; Gholamreza Gohari; et al. (Science of The Total Environment, 2023)

A systematic review of physiological signals based driver drowsiness detection systems - Adil Ali Saleem; Hafeez Ur Rehman Siddiqui; Muhammad Amjad Raza; Furqan Rustam; Sandra Dudley; Imran Ashraf (Cognitive Neurodynamics, 2023)

Shortening harvest interval, reaping benefits? A study on harvest practices in oil palm smallholder farming systems in Indonesia - Rosanne E. de Vos; Lisa Nurfalah; Fatima A. Tenorio; Ya Li Lim; Juan P. Monzon; Christopher R. Donough; Hendra Sugianto; Asri A. Dwiyahreni; Nurul L. Winarni; Nadia Mulani; Gilang Ramadhan; Muhammad Ali Imran; et al. (Agricultural Systems, 2023)

Alleviation of arsenic toxicity-induced oxidative stress in lemon grass by methyl jasmonate - Khansa Saleem; Muhammad Ahsan Asghar; Hafiz Hassan Javed; Ali Raza; Mahmoud F. Seleiman; Abd Ullah; Altafur Rahman; Sufyan Iqbal; Aamir Hanif; Shakeel Imran; Sajid Mahmood Nadeem; Junbo Du; et al. (South African Journal of Botany, 2023)

The protective role of tetraploidy and nanoparticles in arsenic-stressed rice: Evidence from RNA sequencing, ultrastructural and physiological studies - Fozia Ghouri; Munazzam Jawad Shahid; Jingwen Liu; Lixia Sun; Muhammad Riaz; Muhammad Imran; Shafaqat Ali; Xiangdong Liu; Muhammad Qasim Shahid (Journal of Hazardous Materials, 2023)

Seed priming with nano-silica effectively ameliorates chromium toxicity in Brassica napus - Zaid Ulhassan; Su Yang; Di He; Ali Raza Khan; Abdul Salam; Wardah Azhar; Sajid Muhammad; Skhawat Ali; Yasir Hamid; Imran Khan; Mohamed Salah Sheteiwy; Weijun Zhou (Journal of Hazardous Materials, 2023)

Exploring the multifunctional roles of quantum dots for unlocking the future of biology and medicine - Muhammad Kashif Ali; Saher Javaid; Haseeb Afzal; Imran Zafar; Kompal Fayyaz; Qurat ul Ain; Mohd Ashraf Rather; Md. Jamal Hossain; Summya Rashid; Khalid Ali Khan; Rohit Sharma (Environmental Research, 2023)

Neem and Castor Oil–Coated Urea Mitigates Salinity Effects in Wheat by Improving Physiological Responses and Plant Homeostasis - Imran Khan; Sadia Muhammad Ali; Muhammad Umer Chattha; Lorenzo Barbanti; Roberta Calone; Athar Mahmood; Tasahil S. Albishi; Muhammad Umair Hassan; Sameer H. Qari (Journal of Soil Science and Plant Nutrition, 2023)
Soil salinity is abiotic stress of growing concern, whose effects can be potentially mitigated by the use of suitable fertilisers. Based on this, an experiment was conducted to determine the role of vegetable oil–coated urea on the performance of wheat ( Triticum aestivum ) under salinity. Neem oil–coated urea (NOCU), castor oil–coated urea (COCU), and normal urea (NU) were compared in wheat plants growing in pots at three soil salinity levels (0, 6, and 12 dS m -1 ). Plant morphology, growth, element contents (Na, Cl, K, and N), and several traits were assessed at the flag leaf stage; biological yield, grain yield, and its components were assessed at maturity. Salinity stunted growth (approximately -50% yield with high salinity vs. control); boosted Na and Cl concentrations while abating K and N concentrations in plant organs; impaired leaf water status; reduced photosynthetic pigments and increased antioxidant activities and osmo-regulating compounds. NOCU and, to a lesser degree, COCU mitigated salinity effects by upgrading antioxidant activities, reducing oxidative stress markers, increasing leaf water status, photosynthetic pigments, and osmo-regulating compounds. However, NOCU under high salinity could only achieve the levels of NU under intermediate salinity. Lastly, NOCU and COCU restricted plant entry of adverse ions (Na and Cl) while increasing K and N accumulation. Vegetable oil–coated urea, namely NOCU, significantly contributed to improving wheat behaviour and final yield under salinity. These outcomes are associated with the two fertilisers’ properties of slow nitrogen release.

Synthesis of Elemental- and Nano-sulfur-enriched Bio-organic Phosphate Composites, and Their Impact on Nutrients Bioavailability and Maize Growth - Ayesha Shakoor; Ghulam Jilani; Tanveer Iqbal; Imran Mahmood; Tajwar Alam; Muhammad Asif Ali; Syed Shahid Hussain Shah; Rizwan Ahmad (Journal of Soil Science and Plant Nutrition, 2023)

Recent insights into pesticide resistance mechanisms in Plutella xylostella and possible management strategies - Muhammad Shehzad; Imran Bodlah; Junaid Ali Siddiqui; Muhammad Adnan Bodlah; Ammara Gull E Fareen; Waqar Islam (Environmental Science and Pollution Research, 2023)

Physical properties of multifunctional TM-doped ZnO nanorods and their photocatalytic and anti-bacterial activities - Yasir Zaman; Muhammad Zahid Ishaque; Yasir Yousaf; Muhammad Shahzad; Abu Bakar Siddique; Muhammad Imran Arshad; Muhammad Sajid; Nisar Ali; Ghulam Nabi (Environmental Science and Pollution Research, 2023)

Diversity in Elemental Content in Selected Artemisia L. (Asteraceae) Species from Gilgit-Baltistan Region of Pakistan Based on Inductively Coupled Plasma Atomic Emission Spectrophotometry (ICP-AES) - Adil Hussain; Muhammad Sajid; Daniel Potter; Hassam Rasheed; Mujtaba Hassan; Naeem Akhtar; Bashir Ahmad; Syed Ali Imran Bokhari (Biological Trace Element Research, 2023)

Variations in cold flow and physical properties of Northern Pakistan gas condensate oil after interacting with different polymeric drilling mud systems - Shaine Mohammadali Lalji; Syed Imran Ali; Sajid Hussain; Syed Muhammad Ali; Zeeshan Ali Lashari (Arabian Journal of Geosciences, 2023)

Application of teleseismic receiver functions and gravity for Moho depth mapping: a case study of the Western Himalayas - Mohammad Salam; Jamil Ahmad; Waqar Ali Zafar; Muhammad Tahir Iqbal; Imran Khan; Amir Sultan; Talat Iqbal (Arabian Journal of Geosciences, 2023)

Screening and growth assessment of indigenous and exotic sesame genotypes under osmotic stress - Jahangir Ahmed; Ghulam Qadir; Muhammad Fraz Ali; Talha Javed; Hafiz Muhammad Jhanzab; Fahad Masoud Wattoo; Imran Mahmood; Muhammad Ansar; Muhammad Akram Khan; Usman Zulfiqar; Bilal Ahamad Paray (South African Journal of Botany, 2023)

An approach to assess offshore wind power potential using bathymetry and near-hub-height reanalysis data - Zia ul Rehman Tahir; Muhammad Abdullah; Sajeer Ahmad; Ammara Kanwal; Muhammad Farhan; Usama Bin Saeed; Tariq Ali; Imran Amin (Ocean Engineering, 2023)

Retraction notice to “Melatonin rescues the mice brain against cisplatin-induced neurodegeneration, an insight into antioxidant and anti-inflammatory effects” [Neurotoxicology 87 (2021) 1–10] - Muhammad Zakria; Nasir Ahmad; Lina Tariq Al Kury; Abdullah Alattar; Zia Uddin; Sami Siraj; Shakir Ullah; Reem Alshaman; Muhammad Imran Khan; Fawad Ali Shah (NeuroToxicology, 2023)

The potential of functionalized graphene-based composites for removing heavy metals and organic pollutants - Muhammad Saqlain Iqbal; Awais Ali Aslam; Ramsha Iftikhar; Muhammad Junaid; Syed Muhammad Imran; Muhammad Shahid Nazir; Zulfiqar Ali; Muhammad Zafar; Ayesha Kanwal; Norinsan Kamil Othman; Ujjwal Pal; Ai Ling Pang; et al. (Journal of Water Process Engineering, 2023)

Integrating by-products from bioenergy technology to improve the morpho-physiological growth and yield of soybean under acidic soil - Muhammad Tayyab Sattar; Ali Raza; Shafaqat Ali; Shanzay Bashir; Farah Kanwal; Imran Khan; Muhammad Ali Raza; Sajad Hussain; Fei Shen (Chemosphere, 2023)

Dynamic spillovers and portfolio risk management between defi and metals: Empirical evidence from the Covid-19 - Shoaib Ali; Muhammad Shahzad Ijaz; Imran Yousaf (Resources Policy, 2023)

Polyvinylpyrrolidone and chitosan-coated magnetite (Fe3O4) nanoparticles for catalytic and antimicrobial activity with molecular docking analysis - Ayesha; Muhammad Imran; Ali Haider; Iram Shahzadi; Sawaira Moeen; Anwar Ul-Hamid; Walid Nabgan; Anum Shahzadi; Thamraa Alshahrani; Muhammad Ikram (Journal of Environmental Chemical Engineering, 2023)

Potential of pectin-chitosan based composite films embedded with quercetin-loaded nanofillers to control meat associated spoilage bacteria - Syed Muhammad Afroz Ali; Taskeen Niaz; Anas Munir; Ramla Shahid; Saima Shabbir; Tayyaba Noor; Muhammad Imran (Food Bioscience, 2023)

Nitrogen Management Strategies to Improve Crop Performance, Recovery Efficiency and Their Relationship with Physiological Indices in Dry Direct-Seeded Rice - Hafeez ur Rehman; Imran Ali; Fiaz Ali; Masood Iqbal Awan; Abdul Wakeel; Muhammad Farooq; Mubshar Hussain (International Journal of Plant Production, 2023)

Pterostilbene reduces the progression of atopic dermatitis via modulating inflammatory and oxidative stress biomarkers in mice - Yasmin Bangash; Ammara Saleem; Muhammad Furqan Akhtar; Fareeha Anwar; Bushra Akhtar; Ali Sharif; Muhammad Imran Khan; Aslam Khan (Inflammopharmacology, 2023)

Numerical investigation of thermal-hydraulic design of a printed circuit steam generator - Muhammad Ali Khan; Syed Anas Sohail; Khalid Waheed; Waseem Siddique; Muhammad Ilyas; Fatih Aydogan; Kamran Rasheed Qureshi; Imran Shaban Bhatti (Annals of Nuclear Energy, 2023)

The co-application of bioslurry and compost with inorganic zinc fertilizer improved soil quality, zinc uptake, and growth of maize crop - Aqarab Husnain Gondal; Muhammad Imran Khan; Sardar Alam Cheema; Muhammad Iftikhar Hussain; Basharat Ali; Muhammad Nawaz; Muhammad Dawood; Ghulam Murtaza (Arabian Journal of Geosciences, 2023)

A comprehensive review on the botany, traditional uses, phytochemistry, pharmacology and toxicity of Anagallis arvensis (L).: A wild edible medicinal food plant - Hammad Saleem; Umair Khurshid; Muhammad Imran Tousif; Sirajudheen Anwar; Nasser A. Awadh Ali; Mohamad Fawzi Mahomoodally; Nafees Ahemad (Food Bioscience, 2023)

The role of shadow economy to determine CO2 emission in Pakistan: evidence from novel dynamic simulated ARDL model and wavelet coherence analysis - Muhammad Ahad; Zulfiqar Ali Imran (Environment, Development and Sustainability, 2023)

Silicon Enhances Morpho–Physio–Biochemical Responses in Arsenic Stressed Spinach (Spinacia oleracea L.) by Minimizing Its Uptake - Muhammad Hamzah Saleem; Manar Fawzi Bani Mfarrej; Aishah Alatawi; Sahar Mumtaz; Muhammad Imran; Muhammad Arslan Ashraf; Muhammad Rizwan; Kamal Usman; Parvaiz Ahmad; Shafaqat Ali (Journal of Plant Growth Regulation, 2023)

Quercetin-loaded chitosan nanoparticles ameliorate adjuvant-induced arthritis in rats by regulating anti-oxidant enzymes and downregulating pro- and inflammatory cytokines - Abdul Hannan; Bushra Akhtar; Ali Sharif; Fozia Anjum; Imran Pasha; Ahrar Khan; Muhammad Furqan Akhtar; Ammara Saleem (Inflammopharmacology, 2023)

Factorial analysis for the impact on filtration properties of water-based drilling fluid after the addition of graphene oxide, pure-bore, and sodium alginate - Shaine Mohammadali Lalji; Syed Imran Ali; Muhammad Mohsin Yousufi; Muhammad Arsalan Sultan; Khizra Fatima; Abdur Rahman Misbah (Arabian Journal of Geosciences, 2023)

Spatial variability of hydrochemistry and health risk assessment of groundwater of taluka Hala, district Matiari, Sindh, Pakistan - Imran Khan Rind; Muhammad Yar Khuhawar; Muhammad Farooque Lanjwani; Taj Muhammad Jahangir Khuhawar; Muhammad Soomar Samtio; Waheed Ali Soomro; Abdul Rehman Baloch (Arabian Journal of Geosciences, 2023)

Experimental design by response surface methodology for efficient cefixime uptake from hospital effluents using anion exchange membrane - Muhammad Ali Khan; Nadeem Raza; Suryyia Manzoor; Ramsha Shuja; Hina Raza; Muhammad Imran Khan; Mudassar Azam; Abdallah Shanableh (Chemosphere, 2023)

Polyelectrolyte multilayers coating of aliphatic polyamide anion-exchange membranes to increase monovalent/divalent anions selectivity in electrodialysis - Muhammad Ahmad; Mahmood Ahmed; Shabbir Hussain; Abid Ali; Manzar Zahra; Muhammad Imran Din; Zeeshan Mustafa (Desalination, 2023)

Biochemical and Physiological Responses of Cucumis sativus Cultivars to Different Combinations of Low-Temperature and High Humidity - Bakht Amin; Muhammad Jawaad Atif; Huanwen Meng; Muhammad Imran Ghani; Muhammad Ali; Xiao Wang; Yuanyuan Ding; Xiuju Li; Zhihui Cheng (Journal of Plant Growth Regulation, 2023)

Occurrence and Distribution of Heavy Metals in Mining Degraded Soil and Medicinal Plants: A Case Study of Pb/Zn Sulfide Terrain Northern Areas, Pakistan - Javed Nawab; Muhammad Idress; Sajid Ullah; Gul Rukh; Rimsha Zainab; Hassan Sher; Junaid Ghani; Sardar Khan; Zahid Ullah; Imran Ahmad; Syed Weqas Ali (Bulletin of Environmental Contamination and Toxicology, 2023)

Heavy metal(loid)s contamination and potential risk assessment via groundwater consumption in the district of Hangu, Pakistan - Imran Ud Din; Said Muhammad; Shah Faisal; Inayat ur Rehman; Wajid Ali (Environmental Science and Pollution Research, 2022)

Molecular epidemiology and characterization of Babesia bovis in cattle of Khyber Pakhtunkhwa province, Pakistan - Muhammad Shoaib; Muhammad Imran Rashid; Haroon Akbar; Ali Ahmad Sheikh; Shahid Hussain Farooqi; Amel Ayari-Akkari; Habab M. Yassin; Rajwali Khan (Tropical Animal Health and Production, 2022)

Pterostilbene improves CFA-induced arthritis and peripheral neuropathy through modulation of oxidative stress, inflammatory cytokines and neurotransmitters in Wistar rats - Ayesha Amin; Muhammad Furqan Akhtar; Ammara Saleem; Ali Sharif; Shahid Shah; Muhammad Imran Khan; Fareeha Anwar; Ghulam Abbas; Hafiz Muhammad Zubair; Muhammad Farhan Sohail (Inflammopharmacology, 2022)

Diversified crop rotation improves continuous monocropping eggplant production by altering the soil microbial community and biochemical properties - Muhammad Imran Ghani; Ahmad Ali; Muhammad Jawaad Atif; Shamina Imran Pathan; Giacomo Pietramellara; Muhammad Ali; Bakht Amin; Zhihui Cheng (Plant and Soil, 2022)

Adenosine A2A receptor as a potential target for improving cancer immunotherapy - Muhammad Atif; Abdullah Alsrhani; Farrah Naz; Muhammad Ikram Ullah; Ayman Ali Mohammed Alameen; Muhammad Imran; Hasan Ejaz (Molecular Biology Reports, 2022)

Mechanisms of β-adrenergic receptors agonists in mediating pro and anti-apoptotic pathways in hyperglycemic Müller cells - Sher Zaman Safi; Laiba Saeed; Humaira Shah; Zahina Latif; Abid Ali; Muhammad Imran; Nawshad Muhammad; Talha Bin Emran; Vetriselvan Subramaniyan; Ikram Shah Bin Ismail (Molecular Biology Reports, 2022)

Correction to: Role of casting and curing conditions on the strength and drying shrinkage of greener concrete - Muhammad Nasir; Adeyemi Adesina; Mohammed Ibrahim; Muhammad Umar Khan; Omar S. Baghabra Al‑Amoudi; Syed Imran Ali; Mohammed Maslehuddin; Khalid Saqer Alotaibi (Environmental Science and Pollution Research, 2022)

Role of casting and curing conditions on the strength and drying shrinkage of greener concrete - Muhammad Nasir; Adeyemi Adesina; Mohammed Ibrahim; Muhammad Umar Khan; Omar S. Baghabra Al-Amoudi; Syed Imran Ali; Mohammed Maslehuddin; Khalid Saqer Alotaibi (Environmental Science and Pollution Research, 2022)

Addressing the effect of meteorological factors and agricultural subsidy on agricultural productivity in India: a roadmap toward environmental sustainability - Imran Ali Baig; Muhammad Irfan; Md. Abdus Salam; Cem Işik (Environmental Science and Pollution Research, 2022)

Spatial green growth in China: exploring the positive role of investment in the treatment of industrial pollution - Muhammad Imran; Naveed Hayat; Muhammad Ali Saeed; Abdul Sattar; Salman Wahab (Environmental Science and Pollution Research, 2022)

Performance analysis of kinetic models in predicting asphaltene precipitation rate under different conditions of temperature and percentage of precipitant molecular weight - Syed Imran Ali; Shaine Mohammadali Lalji; Zahoor Awan; Saud Hashmi; Muhammad Noman; Nimra Yousaf (Arabian Journal of Geosciences, 2022)

Potential of Fish Scale Biochar Nanocomposite with ZnO for Effective Sequestration of Cr (VI) from Water: Modeling and Kinetics - Azhar Ul Islam; Muhammad Mohsin Iqbal; Muhammad Imran; Muhammad Adnan Tariq; Muhammad Nadeem; Muhammad Qasim Kakar; Muhammad Nawaz; Muhammad Amjad; Saeed Ahmad Qaisrani; Muhammad Rizwan; Shafaqat Ali (International Journal of Environmental Research, 2022)

Comparative low lethal effects of three insecticides on demographical traits and enzyme activity of the Spodoptera exigua (Hübner) - Muhammad Hafeez; Farman Ullah; Muhammad Musa Khan; Zhangqian Wang; Hina Gul; Xiaowei Li; Jun Huang; Junaid Ali Siddiqui; Muhammad Qasim; Rui-Long Wang; Muhammad Imran; Mohammed A. Assiri; et al. (Environmental Science and Pollution Research, 2022)

Lethal and sublethal effects of flonicamid (50 WG) and spirotetramat (240 SC) on Bemisia tabaci (Homoptera: Aleyrodidae): an age-stage two sex life table study - Aqsa Abbas; Javaid Iqbal; Ali Zeshan; Qurban Ali; Imran Nadeem; Humaira Malik; Tamsila Nazir; Muhammad Faheem Akhter; Bilal Bin Iqbal (Phytoparasitica, 2022)

RETRACTED ARTICLE: Novel acetamide derivatives of 2-aminobenzimidazole prevent inflammatory arthritis in rats via suppression of pro-inflammatory mediators - Aymun Madni Zubair; Muhammad Nasir Hayat Malik; Waqas Younis; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Alamgeer Yuchi; Muhammad Naveed Mushtaq; Romeeza Tahir; Muhammad Bilal Sarwar; Muhammad Roman; Ayaz Ali Khan; et al. (Inflammopharmacology, 2022)

Methotrexate-loaded biodegradable nanoparticles exert anti-arthritic effect by downregulating pro-inflammatory cytokines in Freund’s complete adjuvant-induced arthritic rats - Muhammad Usman Saleem; Faqir Muhammad; Ali Sharif; Muhammad Imran Arshad; Kanwal Akhtar; Yasir Javed; Bushra Akhtar (Inflammopharmacology, 2022)

Factors associated with cycle threshold values (Ct-values) of SARS-CoV2-rRT-PCR - Naila Shoaib; Naila Noureen; Arwa Faisal; Muhammad Zaheer; Muhammad Imran; Ali Ahsan; Rimsha Munir; Nousheen Zaidi (Molecular Biology Reports, 2022)

Comprehensive review on naringenin and naringin polyphenols as a potent anticancer agent - Abdur Rauf; Mohammad Ali Shariati; Muhammad Imran; Kashif Bashir; Shahid Ali Khan; Saikat Mitra; Talha Bin Emran; Kamala Badalova; Md. Sahab Uddin; Mohammad S. Mubarak; Abdullah S. M. Aljohani; Fahad A. Alhumaydhi; et al. (Environmental Science and Pollution Research, 2022)

Exploring the potential effect of Achnatherum splendens L.–derived biochar treated with phosphoric acid on bioavailability of cadmium and wheat growth in contaminated soil - Muhammad Irfan; Khadim Dawar; Shah Fahad; Imran Mehmood; Saud Alamri; Manzer H. Siddiqui; Shah Saud; Jabar Zaman Khan Khattak; Shamsher Ali; Shah Hassan; Taufiq Nawaz; Hafiz Mohkum Hammad; et al. (Environmental Science and Pollution Research, 2022)

Controlling of Xanthomonas axonopodis pv. phaseoli by induction of phenolic compounds in bean plants using salicylic and benzoic acids - Kamal A. M. Abo-Elyousr; Muhammad Imran; Najeeb M. Almasoudi; Esmat F. Ali; Sabry Hassan; Nashwa M A. Sallam; Khamis Youssef; Ismail R. Abdel-Rahim; Hadeel M.M. Khalil Bagy (Journal of Plant Pathology, 2022)

3-Dimensional membrane capsules: Synthesis modulations for the remediation of environmental pollutants – A critical review - Imran Ali; Juying Li; Changsheng Peng; Muhammad Qasim; Zahid M. Khan; Iffat Naz; Muhammad Sultan; Muhammad Rauf; Waheed Iqbal; Hafiz Muhammad Adeel Sharif (Critical Reviews in Environmental Science and Technology, 2022)

Range extension and species confirmation of Rhyneptesicus nasutus (Sind Serotine Bat) (Mammalia:Chiroptera) from Bajaur Agency, FATA, Pakistan - Muhammad Idnan; Sajid Mansoor; Muhammad Babar Khawar; Arshad Javid; Ali Hussain; Muhammad Imran; Arif Ullah (Molecular Biology Reports, 2022)

Impact of shadow economy on renewable and nonrenewable energy consumption in Pakistan: evidence from quantile cointegration and causality analysis - Muhammad Ahad; Zulfiqar Ali Imran; Hira Aftab (Environmental Science and Pollution Research, 2022)

Sustainability and efficiency analysis w.r.t adoption of climate-smart agriculture (CSA) in Pakistan: a group-wise comparison of adopters and conventional farmers - Muhammad Ali Imran; Asghar Ali; Richard J. Culas; Muhammad Ashfaq; Irfan Ahmad Baig; Shoaib Nasir; Arshad Hussain Hashmi (Environmental Science and Pollution Research, 2022)

Correction to: Molecular detection of Cryptosporidium: an emerging parasite in different water sources of 2010 flood‑affected district Nowshera, Pakistan - Shaukat Ali Khan; Imran Khan; Izaz Ali; Amir Muhammad Khan; Muhammad Anees; Khurshaid Ali Khan; Wajid Rashid; Noorul Akbar (Archives of Microbiology, 2022)

Insect pests of economic importance attacking wheat crop (Triticum aestivum L.) in Punjab, Pakistan - Dilbar Hussain; Muhammad Asrar; Bushra Khalid; Faisal Hafeez; Muhammad Saleem; Muazzma Akhter; Maqsood Ahmed; Imran Ali; Kanwal Hanif (International Journal of Tropical Insect Science, 2022)

Soil conditioners improve rhizodegradation of aged petroleum hydrocarbons and enhance the growth of Lolium multiflorum - Fida Hussain; Aqib Hassan Ali Khan; Imran Hussain; Asifa Farooqi; Yousaf Shad Muhammad; Mazhar Iqbal; Muhammad Arslan; Sohail Yousaf (Environmental Science and Pollution Research, 2022)

Moderating role of institutional quality in validation of pollution haven hypothesis in BRICS: a new evidence by using DCCE approach - Imran Sharif Chaudhry; Weihua Yin; Syed Ahtsham Ali; Muhammad Faheem; Qaiser Abbas; Fatima Farooq; Saeed Ur Rahman (Environmental Science and Pollution Research, 2022)

Growth prediction of Alternanthera philoxeroides under salt stress by application of artificial neural networking - Qaiser Javed; Ahmad Azeem; Jianfan Sun; Ikram Ullah; Daolin Du; Muhammad Ali Imran; Muhammad Imran Nawaz; Hassan T. Chattha (Plant Biosystems, 2022)

Phenomena, factors of wax deposition and its management strategies - Syed Imran Ali; Shaine Mohammadali Lalji; Javed Haneef; Muhammad Arqam Khan; Mohsin Yousufi; Nimra Yousaf; Abdus Saboor (Arabian Journal of Geosciences, 2022)

Impact of invasive ant species on native fauna across similar habitats under global environmental changes - Junaid Ali Siddiqui; Bamisope Steve Bamisile; Muhammad Musa Khan; Waqar Islam; Muhammad Hafeez; Imran Bodlah; Yijuan Xu (Environmental Science and Pollution Research, 2021)

Paclobutrazol Improves Sesame Yield by Increasing Dry Matter Accumulation and Reducing Seed Shattering Under Rainfed Conditions - Muhammad Zeeshan Mehmood; Ghulam Qadir; Obaid Afzal; Atta Mohi Ud Din; Muhammad Ali Raza; Imran Khan; Muhammad Jawad Hassan; Samrah Afzal Awan; Shakeel Ahmad; Muhammad Ansar; Muhammad Aqeel Aslam; Mukhtar Ahmed (International Journal of Plant Production, 2021)
Several biotic and abiotic stresses significantly decrease the biomass accumulation and seed yield of sesame crops under rainfed areas. However, plant growth regulators (such as Paclobutrazol) can improve the total dry matter and seed production of the sesame crop. The effects of the paclobutrazol application on dry matter accumulation and seed yield had not been studied before in sesame under rainfed conditions. Therefore, a two-year field study during 2018 and 2019 was conducted with key objectives to assess the impacts of paclobutrazol on leaf greenness, leaf area, total dry matter production and partitioning, seed shattering, and seed yield of sesame. Two sesame cultivars (TS-5 and TS-3) were treated with four paclobutrazol concentrations (P0 = Control, P1 = 100 mg L −1 , P2 = 200 mg L −1 , P3 = 300 mg L −1 ). The experiment was executed in RCBD-factorial design with three replications. Compared with P0, treatment P3 improved the leaf greenness of sesame by 17%, 38%, and 60% at 45, 85, and 125 days after sowing, respectively. However, P3 treatment decreased the leaf area of sesame by 14% and 20% at 45 and 85 days after sowing than P0, respectively. Compared with P0, treatment P3 increased the leaf area by 46% at 125 days after sowing. On average, treatment P3 also improved the total biomass production by 21% and partitioning in roots, stems, leaves, capsules, and seeds by 23%, 19%, 23%, 22%, and 40%, respectively, in the whole growing seasons as compared to P0. Moreover, under P3 treatment, sesame attained the highest seed yield and lowest seed shattering by 27% and 30%, respectively, compared to P0. This study indicated that by applying the paclobutrazol concentration at the rate of 300 mg L −1 in sesame, the leaf greenness, leaf areas, biomass accumulation, partitioning, seed yield, and shatter resistance could be improved. Thus, the optimum paclobutrazol level could enhance the dry matter accumulation and seed production capacity of sesame by decreasing shattering losses under rainfed conditions.

Characterization and sensitivity of Botrytis cinerea to benzimidazole and succinate dehydrogenase inhibitors fungicides, and illustration of the resistance profile - Muhammad Imran; Esmat F. Ali; Sabry Hassan; Kamal A. M. Abo-Elyousr; Nashwa MA. Sallam; Muhammad Muntazir Mehdi Khan; Muhammad Waqas Younas (Australasian Plant Pathology, 2021)

An in vitro antiviral activity of iodine complexes against SARS-CoV-2 - Imran Altaf; Muhammad Faisal Nadeem; Nadir Hussain; Muhammad Nawaz; Sohail Raza; Muhammad Abu bakr Shabbir; Muhammad Adnan Ashraf; Muhammad Asad Ali; Sohail Hassan; Muhammad Waqar Aziz; Nazish Matti; Muhammad Ashraf; et al. (Archives of Microbiology, 2021)

Molecular detection of Cryptosporidium: an emerging parasite in different water sources of 2010 flood-affected district Nowshera, Pakistan - Shaukat Ali Khan; Imran Khan; Izaz Ali; Amir Muhammad Khan; Muhammad Anees; Khurshaid Ali Khan; Wajid Rashid; Noorul Akbar (Archives of Microbiology, 2021)

Compact maize canopy improves radiation use efficiency and grain yield of maize/soybean relay intercropping system - Muhammad Ali Raza; Liang Cui; Imran Khan; Atta Mohi Ud Din; Guopeng Chen; Muhammad Ansar; Mukhtar Ahmed; Shakeel Ahmad; Abdul Manaf; John Kwame Titriku; Ghulam Abbas Shah; Feng Yang; et al. (Environmental Science and Pollution Research, 2021)

Livelihood diversification in managing catastrophic risks: evidence from flood-disaster regions of Khyber Pakhtunkhwa Province of Pakistan - Ashfaq Ahmad Shah; Zaiwu Gong; Nasir Abbas Khan; Imran Khan; Muhammad Ali; Syed Asif Ali Naqvi (Environmental Science and Pollution Research, 2021)

Regional disparities in Preventive measures of COVID-19 pandemic in China. A study from international students’ prior knowledge, perception and vulnerabilities - Ijaz Younis; Cheng Longsheng; Muhammad Imran Zulfiqar; Muhammad Imran; Syed Ahsan Ali Shah; Mudassar Hussain; Yasir Ahmed Solangi (Environmental Science and Pollution Research, 2021)

Application of an improved multifractal detrended fluctuation analysis approach for estimation of the complexity of daily precipitation - Liangliang Zhang; Heng Li; Dong Liu; Qiang Fu; Mo Li; Muhammad Abrar Faiz; Shoaib Ali; Muhammad Imran Khan; Tianxiao Li (International Journal of Climatology, 2021)
Affected by climate change and high‐intensity human activities, the precipitation series is characterized by nonlinear complex fluctuations. In order to accurately quantify the precipitation complexity, the complete ensemble empirical mode decomposition with adaptive noise (CEEMDAN) method was introduced to address the shortcomings of the traditional multifractal detrended fluctuation analysis (MFDFA), and the CEEMDAN‐MFFA method was proposed to explore the spatiotemporal variability and possible causes of precipitation complexity in Northeast China (NEC). The results showed that the traditional MFDFA method generally overestimated precipitation complexity. However, the CEEMDAN‐MFFA method improved the accuracy and reliability of precipitation complexity analysis. Daily precipitation series in NEC were characterized by multifractal with high uncertainty and anti‐persistence. The lowest precipitation complexity was 0.573, which appeared in Qian'an, Jilin Province, and the highest precipitation complexity was 1.108, which appeared in the Boketu, Inner Mongolia. The cities with high complexity of daily precipitation are sporadically distributed in the three provinces of Heilongjiang, Jilin and Liaoning. The average complexity is ~0.892, accounting for 22.5% of the total administrative districts. The complexity of daily precipitation showed a statistically insignificant downward trend with time. The precipitation dynamics structure in the southeast and northwest of the study area was complex, and the precipitation was less predictable than other regions. However, the precipitation dynamics structure was relatively simple and the precipitation was easily predictable in the northeastern, central and southwestern regions. Elevation, topographic relief, changes in water area, forest area and agricultural production were the main influencing factors for the differences in precipitation complexity. Results also revealed that increasing the area of forestland by means of protecting and breeding forests, via regulation of the forest ecosystems to alleviate the complex precipitation process will become a reliable approach to cope with nonstationary precipitation.

Does the adaptation of climate-smart agricultural practices increase farmers’ resilience to climate change? - Ihsan Jamil; Wen Jun; Bushra Mughal; Muhammad Haseeb Raza; Muhammad Ali Imran; Ali Waheed (Environmental Science and Pollution Research, 2021)

In vitro differentiation effect of CCL4-induced liver injured mice serum on bone marrow-derived mesenchymal stem cells toward hepatocytes like cells - Sulaiman Shams; Nazia Imran; Sahib Gul Afridi; Muhammad Ayaz; Atif Ali Khan Khalil; Abdul Nasir (Cell and Tissue Banking, 2021)

Alkaline lipase production by novel meso-tolerant psychrophilic Exiguobacterium sp. strain (AMBL-20) isolated from glacier of northeastern Pakistan - Muhammad Talha Yasin; Yasir Ali; Khurshid Ahmad; Abdul Ghani; Kinza Amanat; Muhammad Mudassir Basheir; Muhammad Faheem; Saddam Hussain; Bashir Ahmad; Adil Hussain; Syed Ali Imran Bokhari (Archives of Microbiology, 2021)

Can sulphur improve the nutrient uptake, partitioning, and seed yield of sesame? - Muhammad Zeeshan Mehmood; Obaid Afzal; Mukhtar Ahmed; Ghulam Qadir; Ahmed M.S. Kheir; Muhammad Aqeel Aslam; Atta Mohi Ud Din; Imran Khan; Muhammad Jawad Hassan; Tehseen Ahmad Meraj; Muhammad Ali Raza; Shakeel Ahmad (Arabian Journal of Geosciences, 2021)
Sulphur (S) is considered to improve the nutrient uptake of plants due to its synergistic relationship with other nutrients. This could ultimately enhance the seed yield of oilseed crops. However, there is limited quantitative information on nutrient uptake, distribution, and its associated impacts on seed yield of sesame under the S application. Thus, a two-year field study (2018 and 2019) was conducted to assess the impacts of different S treatments (S 0 = Control, S 20 = 20, S 40 = 40, and S 60 = 60 kg ha −1 ) on total dry matter production, nitrogen, phosphorus, potassium, S uptake and distribution at the mid-bloom stage and physiological maturity. Furthermore, treatment impacts were studied on the number of capsules per plant, number of seeds per capsule, thousand seed weight, and seed yield at physiological maturity in sesame. Compared to S 0 , over the years, treatment S 40 significantly increased the total uptake of nitrogen, phosphorus, potassium, and S (by 13, 22, 11% and 16%, respectively) at physiological maturity, while their distribution by 13, 36, 14, and 24% (in leaves), 12, 15, 11, and 15% (in stems), 15, 42, 18, and 10% (in capsules), and 14, 22, 9, and 15% (in seeds), respectively. Enhanced nutrient uptake and distribution in treatment S 40 improved the total biomass accumulation (by 28%) and distribution in leaves (by 34%), stems (by 27%), capsules (by 26%), and seeds (by 28%), at physiological maturity, as compared to S 0 . Treatment S 40 increased the number of capsules per plant (by 13%), number of seeds per capsule (by 11%), and thousand seed weight (by 6%), compared to S 0 . Furthermore, over the years, relative to control, sesame under S 40 had a higher seed yield by 28% and enhanced the net economic returns by 44%. Thus, our results suggest that optimum S level at the time of sowing improves the nutrient uptake and distribution during the plant lifecycle, which ultimately enhances total dry matter accumulation, seed yield, and net productivity of sesame.

Growth and Physiology of Maize (Zea mays L.) in a Nickel-Contaminated Soil and Phytoremediation Efficiency Using EDTA - Muhammad Imran Tipu; Muhammad Yasin Ashraf; Nadeem Sarwar; Muhammad Akhtar; Muhammad Rashid Shaheen; Sajjad Ali; Christos A. Damalas (Journal of Plant Growth Regulation, 2021)

Pomegranate as a source of bioactive constituents: a review on their characterization, properties and applications - Maryam Pirzadeh; Nicola Caporaso; Abdur Rauf; Mohammad Ali Shariati; Zhanibek Yessimbekov; Muhammad Usman Khan; Muhammad Imran; Mohammad S. Mubarak (Critical Reviews in Food Science and Nutrition, 2021)

Heat stress in cultivated plants: nature, impact, mechanisms, and mitigation strategies—a review - Muhammad Umair Hassan; Muhammad Umer Chattha; Imran Khan; Muhammad Bilal Chattha; Lorenzo Barbanti; Muhammad Aamer; Muhammad Mehmood Iqbal; Muhammad Nawaz; Athar Mahmood; Abid Ali; Muhammad Talha Aslam (Plant Biosystems, 2021)

Appraisal of One Health approach amid COVID-19 and zoonotic pandemics: insights for policy decision - Muhammad Imran Arshad; Hilal Ahmad Khan; Bilal Aslam; Junaid Ali Khan (Tropical Animal Health and Production, 2021)

Re-biodegradation of all alkanes after chemical oxidation in soils - Jinlan Xu; Yanliang Dong; Yuanyuan Zheng; Peiqi Fan; Lu Xu; Xue Qiao; Muhammad Ali Imran (Journal of Soils and Sediments, 2021)

Silver nanoparticles improved the plant growth and reduced the sodium and chlorine accumulation in pearl millet: a life cycle study - Imran Khan; Samrah Afzal Awan; Muhammad Ali Raza; Muhammad Rizwan; Rezwan Tariq; Shafaqat Ali; Linkai Huang (Environmental Science and Pollution Research, 2021)

Correction to: Effect of Endoxylanase and Iron Oxide Nanoparticles on Performance and Histopathological Features in Broilers - Hamza Rehman; Muzamal Akram; Mubin Mustafa Kiyani; Muhammad Talha Yasin; Abdul Ghani; Javed Iqbal Saggu; Syed Sajid Hussain Shah; Zafar Mahmood Khalid; Syed Ali Imran Bokhari (Biological Trace Element Research, 2021)

Role of fruit volatiles of different guava varieties in attraction and oviposition behaviors of peach fruit fly, Bactrocera zonata Saunders - Muhammad Binyameen; Abdul Hamid; Imran Afzal; Muhammad Sajjad; Muhammad Azeem; Syed Muhammad Zaka; Zahid Mehmood Sarwar; Sarfraz Ali Shad; Thomas C. Baker; Fredrik Schlyter (Arthropod-Plant Interactions, 2021)

Artemisia chamaemelifolia Vill: a rare species of genus Artemisia (Asteraceae-Anthemideae) now present in the northeast (Gilgit-Baltistan) region of Pakistan - Adil Hussain; Muhammad Qasim Hayat; Syed Ali Imran Bokhari (Biologia, 2021)

Molybdenum Application Regulates Oxidative Stress Tolerance in Winter Wheat Under Different Nitrogen Sources - Muhammad Imran; Xuecheng Sun; Saddam Hussain; Usman Ali; Muhammad Shoaib Rana; Fahd Rasul; Shadab Shaukat; Chengxiao Hu (Journal of Soil Science and Plant Nutrition, 2020)

Synthesis, Structure Study, First-Principles Investigations and Luminescence Properties of Europium and Terbium Complexes - Bakhat Ali; Helio A. Stefani; Muhammad Imran; Ahmad Irfan; Mohammed A. Assiri; Maria Claudia F. C. Felinto; Muhammad Khalid; Abdullah G. Al-Sehemi (Journal of Fluorescence, 2020)

Combined application of Bacillus sp. MN-54 and phosphorus improved growth and reduced lead uptake by maize in the lead-contaminated soil - Muhammad Junaid Afzal; Muhammad Imran Khan; Sardar Alam Cheema; Saddam Hussain; Muhammad Anwar-ul-Haq; Muhammad Hayder Ali; Muhammad Naveed (Environmental Science and Pollution Research, 2020)

Potentially toxic elements’ occurrence and risk assessment through water and soil of Chitral urban environment, Pakistan: a case study - Inayat ur Rehman; Muhammad Ishaq; Liaqat Ali; Said Muhammad; Imran Ud Din; Muhammad Yaseen; Hameed Ullah (Environmental Geochemistry and Health, 2020)

Analyzing adaptation strategies for maize production under future climate change in Guanzhong Plain, China - Qaisar Saddique; Huanjie Cai; Jiatun Xu; Ali Ajaz; Jianqiang He; Qiang Yu; Yunfei Wang; Hui Chen; Muhammad Imran Khan; De Li Liu; Liang He (Mitigation and Adaptation Strategies for Global Change, 2020)

Single tube multiplex PCR assay for the identification of banned meat species - Memoona Iqbal; Muhammad Sulyman Saleem; Muhammad Imran; Waseem Ahmad Khan; Kamran Ashraf; M. Yasir Zahoor; Imran Rashid; Habib-Ur Rehman; Asif Nadeem; Saadat Ali; Sarwat Naz; Wasim Shehzad (Food Additives & Contaminants Part B-Surveillance, 2020)

Changes in Soil Organic Carbon Fractions Across a Loess Toposequence - Arsalan Azam; Mohammad Saleem Akhtar; Shah Rukh; Ayaz Mehmood; Muhammad Imran; Ahmad Khan; Abdul Qayyum; Waseem Ahmad; Ali Raza Gurmani (Journal of Soil Science and Plant Nutrition, 2020)

Growth, Biomass Production, and Yield Potential of Quinoa (Chenopodium quinoa Willd.) as Affected by Planting Techniques Under Irrigated Conditions - Saif Ali; Muhammad Umer Chattha; Muhammad Umair Hassan; Imran Khan; Muhammad Bilal Chattha; Babar Iqbal; Muzammal Rehman; Muhammad Nawaz; Muhammad Zubair Amin (International Journal of Plant Production, 2020)

RETRACTED ARTICLE: Trilemma assessment of energy intensity, efficiency, and environmental index: evidence from BRICS countries - Zulifqar Ali Baloch; Qingmei Tan; Nadeem Iqbal; Muhammad Mohsin; Qaiser Abbas; Wasim Iqbal; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2020)

Effective sequestration of Cr (VI) from wastewater using nanocomposite of ZnO with cotton stalks biochar: modeling, kinetics, and reusability - Muhammad Adnan Tariq; Muhammad Nadeem; Muhammad Mohsin Iqbal; Muhammad Imran; Muhammad Hussnain Siddique; Zafar Iqbal; Muhammad Amjad; Muhammad Rizwan; Shafaqat Ali (Environmental Science and Pollution Research, 2020)

Formulation Development, Characterization, and Evaluation of a Novel Dexibuprofen-Capsaicin Skin Emulgel with Improved In Vivo Anti-inflammatory and Analgesic Effects - Imran Khan Burki; Muhammad Khalid Khan; Barkat Ali Khan; Bushra Uzair; Valdir A. Braga; Qazi Adnan Jamil (AAPS PharmSciTech, 2020)

Litter decay in rangeland sites with varying history of human disturbance: a study with Hazargangi Chiltan mountain - Imran Khan; Shamim Gul; Sarfraz Ahmad; Gul Bano Rehman; Agha Waqar Yunus; Iram Gul; Imran Ali; Ali Akbar; Muhammad Islam (Journal of Mountain Science, 2020)

Temperature trends and elevation dependent warming during 1965–2014 in headwaters of Yangtze River, Qinghai Tibetan Plateau - Naveed Ahmed; Gen-xu Wang; Adeyeri Oluwafemi; Sarfraz Munir; Zhao-yong Hu; Aamir Shakoor; Muhammad Ali Imran (Journal of Mountain Science, 2020)

Lipids as biomarkers of brain disorders - Ghulam Hussain; Haseeb Anwar; Azhar Rasul; Ali Imran; Muhammad Qasim; Shamaila Zafar; Muhammad Imran; Syed Kashif Shahid Kamran; Nimra Aziz; Aroona Razzaq; Waseem Ahmad; Asghar Shabbir; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Inhibition of Hyperuricemia and Gouty Arthritis in BALB/c Mice Using Copper Oxide Nanoparticles - Mubin Mustafa Kiyani; Hamza Rehman; Mir Arif Hussain; Saira Jahan; Muhammad Afzal; Irum Nawaz; Tariq Mahmood; Syed Ali Imran Bokhari (Biological Trace Element Research, 2020)

Genome Wide Identification and Expression Profiles of TALE Genes in Pineapple (Ananas comosus L) - Hina Ali; Yanhui Liu; Syed Muhammad Azam; Imran Ali; Umair Ali; Weimin Li; Hafiza Javaria Ashraf; Yang Jie; Stefan Olsson; Yuan Qin (Tropical Plant Biology, 2019)

Impact assessment of land use change on surface temperature and agricultural productivity in Peshawar-Pakistan - Imran Khan; Tehseen Javed; Ahmad Khan; Hongdou Lei; Ihsan Muhammad; Imad Ali; Xuexi Huo (Environmental Science and Pollution Research, 2019)

A cross-sectional study of methicillin-resistant Staphylococcus aureus at the equine-human interface - Namra Waqar; Quratulain Amin; Tariq Munir; Muhammad Sohaib Ikram; Naveed Shahzad; Arkim Mirza; Arshad Ali; Muhammad Imran Arshad (Tropical Animal Health and Production, 2019)

Composted Sugarcane By-product Press Mud Cake Supports Wheat Growth and Improves Soil Properties - Muhammad Umer Chattha; Muhammad Umair Hassan; Lorenzo Barbanti; Muhammad Bilal Chattha; Imran Khan; Muhammad Usman; Abid Ali; Muhammad Nawaz (International Journal of Plant Production, 2019)

Spatial heterogeneity of ecosystem services: a distance decay approach to quantify willingness to pay for improvements in Heihe River Basin ecosystems - Sufyan Ullah Khan; Imran Khan; Minjuan Zhao; Hsiaoping Chien; Qian Lu; Muhammad Abu Sufyan Ali; Arshad Ahmad Khan; Shah Fahad (Environmental Science and Pollution Research, 2019)

PEGylation: a promising strategy to overcome challenges to cancer-targeted nanomedicines: a review of challenges to clinical transition and promising resolution - Zahid Hussain; Shahzeb Khan; Muhammad Imran; Muhammad Sohail; Syed Wadood Ali Shah; Marcel de Matas (Drug Delivery and Translational Research, 2019)

Different ambient management intervention techniques and their effect on milk production and physiological parameters of lactating NiliRavi buffaloes during hot dry summer of subtropical region - Mehtab Ahmad; Jalees Ahmed Bhatti; Muhammad Abdullah; Rahman Ullah; Qurat ul Ain; Muhammad Sajid Hasni; Mahboob Ali; Abdul Rashid; Imran Qaisar; Ghazunfar Rashid; Rafi Uddin (Tropical Animal Health and Production, 2019)

Nickel toxicity in plants: reasons, toxic effects, tolerance mechanisms, and remediation possibilities—a review - Muhammad Umair Hassan; Muhammad Umer Chattha; Imran Khan; Muhammad Bilal Chattha; Muhammad Aamer; Muhammad Nawaz; Abid Ali; Muhammad Aman Ullah Khan; Tahir Abbas Khan (Environmental Science and Pollution Research, 2019)

Role of phosphorous mining in mobilization and bioaccessibility of heavy metals in soil-plant system: Abbottabad, Pakistan - Afshan; Sajjad Ahmad; Muhammad Imran; Rab Nawaz; Muhammad Arshad; Muhammad Ejaz Ul Islam Dar; Muhammad Hussnain Siddque; Muhammad Nadeem; Liaqat Ali (Arabian Journal of Geosciences, 2019)

Domperidone nanocrystals with boosted oral bioavailability: fabrication, evaluation and molecular insight into the polymer-domperidone nanocrystal interaction - Stalielson Tatenda Ndlovu; Naseem Ullah; Shahzeb Khan; Pritika Ramharack; Mahmoud Soliman; Marcel de Matas; Muhammad Shahid; Muhammad Sohail; Muhammad Imran; Syed Wadood Ali Shah; Zahid Hussain (Drug Delivery and Translational Research, 2019)

Foliar- and soil-applied salicylic acid and bagasse compost addition to soil reduced deleterious effects of salinity on wheat - Muhammad Imran Khan; Muhammad Aqeel Shoukat; Sardar Alam Cheema; Shafaqat Ali; Muhammad Azam; Muhammad Rizwan; Rashad Qadri; Mohammad I. Al-Wabel (Arabian Journal of Geosciences, 2019)

Isolation, characterization and efficacy of phage MJ2 against biofilm forming multi-drug resistant Enterobacter cloacae - Muhsin Jamal; Saadia Andleeb; Fazal Jalil; Muhammad Imran; Muhammad Asif Nawaz; Tahir Hussain; Muhammad Ali; Sadeeq ur Rahman; Chythanya Rajanna Das (Folia Microbiologica, 2019)

Deadly outbreak of chickenpox at district Faisalabad, Pakistan: possible causes, and preventive way forward - Muhammad Zubair Yousaf; Sadia Zia; Khalid Mahmood Anjum; Usman Ali Ashfaq; Muhammad Imran; Samia Afzal; Muhammad Sarfaraz Iqbal (Molecular Biology Reports, 2018)

Endophytic fungus Paecilomyces formosus LHL10 produces sester-terpenoid YW3548 and cyclic peptide that inhibit urease and α-glucosidase enzyme activities - Saqib Bilal; Liaqat Ali; Abdul Latif Khan; Raheem Shahzad; Sajjad Asaf; Muhammad Imran; Sang-Mo Kang; Sang-Kuk Kim; In-Jung Lee (Archives of Microbiology, 2018)

Ciprofloxacin: from infection therapy to molecular imaging - Syed Ali Raza Naqvi; Samina Roohi; Anam Iqbal; Tauqir A. Sherazi; Ameer Fawad Zahoor; Muhammad Imran (Molecular Biology Reports, 2018)

Effect of biochar and quicklime on growth of wheat and physicochemical properties of Ultisols - Zaffar Malik; Zong Yutong; Lu ShengGao; Ghulam Hassan Abassi; Shafaqat Ali; Muhammad Imran khan; Muhammad Kamran; Moazzam Jamil; Mohammad I. Al-Wabel; Muhammad Rizwan (Arabian Journal of Geosciences, 2018)

A novel mutation in RDH5 gene causes retinitis pigmentosa in consanguineous Pakistani family - Neelam Sultan; Irfan Ali; Shazia Anwer Bukhari; Shahid Mahmood Baig; Muhammad Asif; Muhammad Qasim; Muhammad Imran Naseer; Mahmood Rasool (Genes & Genomics, 2018)

Effective Bioremediation of Endocrine-Disrupting Phthalate Esters, Mediated by Bacillus Strains - Muhammad Ali Surhio; Farah N. Talpur; Shafi M. Nizamani; Marvi Kanwal Talpur; Farah Amin; Abid Ali Khaskheli; Shazia Bhurgri; Hassan Imran Afridi; Shafiq Ur Rahman (Water, Air, & Soil Pollution, 2017)

Statistical methodology for biosorption of nitrate (NO3 −) ions from aqueous solution by Pleurotus eryngii fungal biomass - Farah Amin; Farah Naz Talpur; Aamna Balouch; Hassan Imran Afridi; Muhammad Ali Surhio (Modeling Earth Systems and Environment, 2017)

Leaching of phthalate esters from different drinking stuffs and their subsequent biodegradation - Muhammad Ali Surhio; Farah N. Talpur; Shafi M. Nizamani; Marvi Kanwal Talpur; Hassan Imran Afridi; Abid Ali Khaskheli; Shazia Bhurgri; Junaid Ali Surhio (Environmental Science and Pollution Research, 2017)

Phenacyl group containing amide derivative of dehydroabietylamine exhibiting enhanced cytotoxic activity against PLC and MCF7 cancer cell lines - Muhammad Ayaz Mustufa; Afshan Aslam; Cigdem Ozen; Imran Ali Hashmi; Naim ul Hasan Naqvi; Mehmet Ozturk; Firdous Imran Ali (Medicinal Chemistry Research, 2017)

Synthesis of 2-phenyl-1H-imidazo[4,5-b]pyridine as type 2 diabetes inhibitors and molecular docking studies - Muhammad Taha; Nor Hadiani Ismail; Syahrul Imran; Izzatul Ainaa; Manikandan Selvaraj; Mohd syukri baharudin; Muhammad Ali; Khalid Mohammed Khan; Nizam Uddin (Medicinal Chemistry Research, 2017)

Exogenous application of plant growth regulators (PGRs) induces chilling tolerance in short-duration hybrid maize - Muhammad Ahmed Waqas; Imran Khan; Muhammad Javaid Akhter; Mehmood Ali Noor; Umair Ashraf (Environmental Science and Pollution Research, 2017)

Equilibrium modeling of cadmium biosorption from aqueous solution by compost - Iftikhar Ahmad; Muhammad Javed Akhtar; Iram Bashir Khan Jadoon; Muhammad Imran; Muhammad Imran; Shahid Ali (Environmental Science and Pollution Research, 2017)

Comparative Study of Physical Factors and Microbial Diversity of Four Man-Made Extreme Ecosystems - Imran Ali; Ali Akbar; Muhammad Aslam; Sami Ullah; Muhammad Anwar; Hunsa Punnapayak; Pongtharin Lotrakul; Sehanat Prasongsuk; Benjawan Yanwisetpakdee; Ponlada Permpornsakul; Sudip K. Rakshit (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Leaf-based physiological, metabolic, and ultrastructural changes in cultivated cotton cultivars under cadmium stress mediated by glutathione - M. K. Daud; Lei Mei; Azizullah Azizullah; Muhammad Dawood; Imran Ali; Qaisar Mahmood; Waheed Ullah; Muhammad Jamil; S. J. Zhu (Environmental Science and Pollution Research, 2016)

Simultaneously removal of inorganic arsenic species from stored rainwater in arsenic endemic area by leaves of Tecomella undulata: a multivariate study - Kapil Dev Brahman; Tasneem Gul Kazi; Hassan Imran Afridi; Jameel Ahmed Baig; Muhammad Ishaque Abro; Sadaf Sadia Arain; Jamshed Ali; Sumaira Khan (Environmental Science and Pollution Research, 2016)

Prevalence of Waterborne Diseases in Exposed and Unexposed Clusters Using Biosand Filters in a Rural Community, Sindh, Pakistan - Munir Ahmed Sheikh; Muhammad Ayaz Mustufa; Taj Muhammad Laghari; Binafsha Manzoor; Syed Ali Haider; Safia Bibi; Firdous Imran Ali (Exposure and Health, 2016)

Effects of industrial wastewater on growth and biomass production in commonly grown vegetables - Syeda Uzma; Azizullah Azizullah; Roqaia Bibi; Farhat Nabeela; Uzair Muhammad; Imran Ali; Zia Ur Rehman; Donat-Peter Häder (Environmental Monitoring and Assessment, 2016)

Osmoregulation and antioxidant production in maize under combined cadmium and arsenic stress - Shakeel Ahmad Anjum; Mohsin Tanveer; Saddam Hussain; Babar Shahzad; Umair Ashraf; Shah Fahad; Waseem Hassan; Saad Jan; Imran Khan; Muhammad Farrukh Saleem; Ali Ahsan Bajwa; Longchang Wang; et al. (Environmental Science and Pollution Research, 2016)

Toxicity Appraisal of Untreated Dyeing Industry Wastewater Based on Chemical Characterization and Short Term Bioassays - Muhammad Furqan Akhtar; Muhammad Ashraf; Aqeel Javeed; Aftab Ahmad Anjum; Ali Sharif; Ammara Saleem; Bushra Akhtar; Abdul Muqeet Khan; Imran Altaf (Bulletin of Environmental Contamination and Toxicology, 2016)

Correlation studies on nitrogen for sunflower crop across the agroclimatic variability - Wajid Nasim; Hatem Belhouchette; Muhammad Tariq; Shah Fahad; Hafiz Mohkum Hammad; Muhammad Mubeen; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary; Imran Khan; Faisal Mahmood; Tauqeer Abbas; Fahd Rasul; et al. (Environmental Science and Pollution Research, 2016)

Pharmaceutical wastewater being composite mixture of environmental pollutants may be associated with mutagenicity and genotoxicity - Ali Sharif; Muhammad Ashraf; Aftab Ahmed Anjum; Aqeel Javeed; Imran Altaf; Muhammad Furqan Akhtar; Mateen Abbas; Bushra Akhtar; Ammara Saleem (Environmental Science and Pollution Research, 2016)

In vitro anti-oxidant potential of new metabolites from Hypericum oblongifolium (Guttiferae) - Naila Raziq; Muhammad Saeed; Muhammad Shaiq Ali; Salman Zafar; Muhammad Imran Ali (Natural Product Research, 2015)

Development of sediment load estimation models by using artificial neural networking techniques - Muhammad Hassan; M. Ali Shamim; Ali Sikandar; Imran Mehmood; Imtiaz Ahmed; Syed Zishan Ashiq; Anwar Khitab (Environmental Monitoring and Assessment, 2015)

mRNA secondary structure engineering of Thermobifida fusca endoglucanase (Cel6A) for enhanced expression in Escherichia coli - Imran Ali; Rehana Asghar; Sajjad Ahmed; Muhammad Sajjad; Muhammad Tariq; M. Waheed Akhtar (World Journal of Microbiology and Biotechnology, 2015)

Environment and air pollution: health services bequeath to grotesque menace - Muhammad Imran Qureshi; Amran Md. Rasli; Usama Awan; Jian Ma; Ghulam Ali; Faridullah; Arif Alam; Faiza Sajjad; Khalid Zaman (Environmental Science and Pollution Research, 2015)

A Spatial Multi-Criteria Analysis Approach for Locating Suitable Sites for Construction of Subsurface Dams in Northern Pakistan - Imran Ali Jamali; Ulla Mörtberg; Bo Olofsson; Muhammad Shafique (Water Resources Management, 2014)

Cloning and characterization of Na+/H+ antiporter (LfNHX1) gene from a halophyte grass Leptochloa fusca for drought and salt tolerance - Muhammad Rauf; Khurram Shahzad; Rashid Ali; Moddassir Ahmad; Imran Habib; Shahid Mansoor; Gerald A. Berkowitz; Nasir A. Saeed (Molecular Biology Reports, 2014)

Polypharmacy (herbal and synthetic drug combination): a novel approach in the treatment of type-2 diabetes and its complications in rats - Rupinder Kaur; Muhammad Afzal; Imran Kazmi; Iqbal Ahamd; Zubair Ahmed; Babar Ali; Sayeed Ahmad; Firoz Anwar (Journal of Natural Medicines, 2013)

Root colonization and growth promotion of sunflower (Helianthus annuus L.) by phosphate solubilizing Enterobacter sp. Fs-11 - Muhammad Shahid; Sohail Hameed; Asma Imran; Saira Ali; Jan Dirk van Elsas (World Journal of Microbiology and Biotechnology, 2012)

TLR4 polymorphisms and disease susceptibility - Mamoona Noreen; Muhammad Ali A. Shah; Sheeba Murad Mall; Shazia Choudhary; Tahir Hussain; Iltaf Ahmed; Syed Fazal Jalil; Muhammad Imran Raza (Inflammation Research, 2012)

Role of tissue plasminogen activator and plasminogen activator inhibitor polymorphism in myocardial infarction - Waqas Ahmed; Meera Malik; Imran Saeed; Amina Ali Khan; Ahmed Sadeque; Umar Kaleem; Nuzhat Ahmed; Muhammad Ajmal; Maleeha Azam; Raheel Qamar (Molecular Biology Reports, 2011)

Purification and characterization of xylanases from Thermomyces lanuginosus and its mutant derivative possessing novel kinetic and thermodynamic properties - Syed Ali Imran Bokhari; Farooq Latif; Muhammad Ibrahim Rajoka (World Journal of Microbiology and Biotechnology, 2009)